Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2021)
A dataset containing 1100606 species occurrences available in GBIF matching the query: { "and" : [ "HasCoordinate is true", "HasGeospatialIssue is false", "OccurrenceStatus is Present", "Year 2007-2021" ] } The dataset includes 1100606 records from 14856 constituent datasets: 996 records from Suivi des aires marines protégées de Moorea - Invertébrés benthiques. 15 records from Suivi de la colonie de Pipistrelles de la Petite Ceinture à Paris. 1 records from New record of the genus Baetiella Uéno, 1931 (Ephemeroptera: Baetidae) from India with description of a new species and new records for five species. 4 records from Paragoniosomatinae, a new subfamily of Gonyleptidae (Arachnida: Opiliones) based on a new species from the Chapada Diamantina relict cloud forests, Brazil. 1 records from New and little known species of Lepechinella (Crustacea, Amphipoda, Lepechinellidae) and an allied new genus Lepesubchela from the North Atlantic. 1 records from A revision of the species of the Neoserica (sensu lato) vulpes group (Coleoptera: Scarabaeidae: Sericini). 54 records from Aves marinas del atolón Albuquerque durante la Expedición Seaflower 2018 - Proyecto Colombia BIO. 132 records from Herbario del Museo de Historia Natural C.J. Marinkelle. 24645 records from MICA - Muskrat and coypu camera trap observations in Belgium, the Netherlands and Germany. 2 records from A new record of the family Isonychiidae (Insecta: Ephemeroptera) from the Western Ghats, India with a description of new species. 11 records from MEXU/Leguminosae. 5 records from Seven new species and additional records of Palaearctic Leptusa, primarily from Yunnan, China (Coleoptera: Staphylinidae: Aleocharinae). 5 records from The millipede family Polyxenidae (Diplopoda, Polyxenida) in the faunas of the Crimean Peninsula and Caucasus, with notes on other European Polyxenidae. 1 records from Rediscovery of Lestes nigriceps Fraser, 1924 (Odonata: Lestidae) in eastern Cambodia. 52 records from Distribution of Aureoboletus projectellus in Europe. 445 records from Enrichment metagenome. 154 records from Estimación de la densidad poblacional y dieta del lince (Lynx rufus) Sierra Seri, Sonora y Janos, Chihuahua. 5 records from Stomatopod Crustacea of the Austral and Gambier Islands, French Polynesia. 766503 records from Dragonfly records from the British Dragonfly Society Recording Scheme. 208 records from Condamine Alliance. 1 records from The genus Acantholyda (Hymenoptera, Pamphiliidae) of Japan: A revised key and a description of the previously unknown female of Acantholyda flaviventris. 7 records from Revision of the endemic Philippine Poeciloterpa Stål (Hemiptera: Cercopidae) with description of four new species. 181 records from Inventory of natural and agroforestry stands characterized by Xylopia aethiopica (Dunal) A. Rich. (south-Benin). 521 records from Schanzenanlage Bergham. 74 records from Reptiles de la expedición al Río Apaporis - Proyecto Colombia BIO. 14 records from The West Palaearctic Pseudodineura and Endophytus species (Hymenoptera, Tenthredinidae). 3 records from Proctolaelaps species (Acari: Mesostigmata: Melicharidae) from Egypt, with description of a new species and complementary descriptions of other five species. 181 records from Legume Collections of the Plant Genetic Resources Research Institute (CSIR-PGRRI),Ghana. 22 records from Contributions to the study of the grasshopper (Orthoptera: Acrididae Gomphocerinae) courtship songs from Kazakhstan and adjacent territories. 2 records from Two new species of Mendozellus Linnavuori (Hemiptera: Cicadellidae: Deltocephalinae: Deltocephalini) with redescription of Mendozellus asunctia Cheng. 12554 records from Microbial community in marine sediments. 548 records from Données du Geckos vert des Hauts (Phesulma borbonica) du Parc national de La Réunion. 160 records from AVJNF: Søholt Storskov, amphibian survey. 45 records from données espèces - Expertise IPE 63. 1 records from Description of Sweltsa tibetensis sp. n. (Plecoptera: Chloroperlidae) from Tibet Autonomous Region of China. 8 records from Austrolebias ephemerus (Cyprinodontiformes: Rivulidae), a new annual fish from the upper Rio Paraguai basin, Brazilian Chaco. 81 records from Integrative taxonomy of the genus Dyscolus (Coleoptera, Carabidae, Platynini) in Ecuadorian Andes. 941 records from Herbier Louis-Marie (QFA) - Collection de lichens. 1 records from Southern distributional limits of Meliponini bees (Hymenoptera, Apidae) in the Neotropics: taxonomic notes and distribution of Plebeia droryana and P. emerinoides in Argentina. 23 records from On the Staphylinidae of the Greek island Samothraki (Insecta Coleoptera). 1 records from A new Rhopalomeris species (Diplopoda: Glomerida: Glomeridae), and notes on the phylogenetic relationships between glomeridans in Vietnam. 3251 records from Characterizing bumble bee (Bombus) communities in the United States and assessing a conservation monitoring method. 18 records from Chaoborus flavicans Meigen (Diptera, Chaoboridae) is a complex of lake and pond dwelling species: a revision. 3 records from Bees of the Hemihalictus series of Lasioglossum Curtis (Hymenoptera, Halictidae) in South Korea. 6 records from Taxonomy of widespread Neotropical species of Podisus Herrich-Schäffer (Hemiptera: Pentatomidae: Asopinae): redescription of P. distinctus (Stål, 1860) and revalidation of P. fuscescens (Dallas, 1851). 1 records from Two more new species of Hemiphyllodactylus Bleeker (Squamata: Gekkonidae) from the Shan Hills of eastern Myanmar (Burma). 2 records from Updated information on genus Gomphidictinus (Odonata: Gomphidae) in China with description of Gomphidictinus tongi sp. nov.. 59 records from Schulgelände SGD/Viersen. 8 records from Swedish Malaise Trap Project (SMTP) - Dermaptera. 267 records from Données du/de la naturaliste ARNABOLDI Frédéric provenant de la base de donnée du SINP Île-de-France CETTIA. 774 records from Biodiversidad ictica de la Isla Cayo Serranilla Expedición Seaflower 2017 proyecto Colombia BIO. 33 records from New species of the Eastern Hemisphere genera Afroheriades and Noteriades (Hymenoptera, Megachilidae). 1190 records from Coleópteros presentes en un proceso de restauración pasiva en bosque seco tropical. 1 records from A new species and southernmost record of Cestrus Townes (Hymenoptera Ichneumonidae, Cryptinae). 4674 records from Données naturalistes de Ségolène FAUSTEN. 54 records from Distribución, abundancia y efectos nocivos de tres especies de plantas invasoras (Oeceoclades_bonampak). 2 records from Drepanosticta adenani sp. nov., from the Lanjak Entimau Wildlife Sanctuary in Sarawak (Odonata: Zygoptera: Platystictidae). 2 records from New records of phytoseiid mites from Mauritius Island (Acari: Mesostigmata. 152 records from Mushrooms Flora of Nepal at Central Department of Botany, Tribhuvan University, Nepal. 44 records from DMNS Egg Collection (Arctos). 598 records from MZL Invertebrate Collections. 2 records from Microlepidogaster negomata, a new hypoptopomatine catfish (Loricariidae: Hypoptopomatinae) from Rio São Francisco basin, southeastern Brazil. 78 records from A taxonomic revision of the African genus Desplatsia Bocq. (Malvaceae - Grewioideae). 4 records from Four new species of Xiphocentron Brauer, 1870 (Trichoptera: Xiphocentronidae) from the Atlantic Forest, southeastern Brazil. 15 records from Lepidopterous specimens of Yamagata Prefectural Museum. 2 records from Invertebrates of the river Tana Basin in Kenya available at the National Museums of Kenya's Natural History Collections, Invertebrates Zoology Section. 352 records from Loup 2015 présence occasionnelle communale (réseau Loup-Lynx ONCFS). 8 records from Review of the genus Prays Hübner, 1825 (Lepidoptera: Praydidae) from China, with descriptions of twelve new species. 5 records from A new species of Pherbellia (Diptera: Sciomyzidae) from Iran. 1 records from Karpfenteich, Klasse 6d. 2 records from Redescription of Stilobezzia (Stilobezzia) albicoxa Lane & Forattini, 1956 with new synonymy (Diptera: Ceratopogonidae). 485 records from Rothschild Giraffe occurrence records observed at Mwea National Reserve in Central part of Kenya. 42 records from Chronicle of Nature - Phenology of Mushrooms of Pechoro-Ilych State Nature Reserve. 14 records from A review of Scaphisomatini from Sulawesi, with descriptions of ten new species (Coleoptera: Staphylinidae: Scaphidiinae). 191 records from The diversity of the genus Aricidea (Polychaeta: Paraonidae) from the Sea of Marmara, with descriptions of two new species and two new records for the Mediterranean fauna. 5750 records from Vegetation Relevés of Main Vegetation Types of the Prioksko-Terrasnyi Biosphere Reserve (2020). 21 records from Revision of New World Cosmorrhyncha Meyrick, 1913 (Lepidoptera: Tortricidae: Olethreutinae), with descriptions of five new species. 1 records from Unveiling the morphology of the Oriental rare monotypic ant genus Opamyrma YAMANE, BUI & EGUCHI, 2008 (Hymenoptera: Formicidae: Leptanillinae) and its evolutionary implications, with first descriptions of the male, larva, tentorium, and sting apparatus. 544 records from Ensemble des données Rhopalocères. 83803 records from Florida Keys Reef Visual Census 2014. 8 records from Troglocoelotes gen. n., a new genus of Coelotinae spiders (Araneae, Agelenidae) from caves in South China. 5 records from The InBIO Barcoding Initiative Database: DNA Barcoding reveals sexual dimorphism in Isotrias penedana Trematerra, 2013 (Lepidoptera: Tortricidae, Chlidanotinae). 15 records from Monitoreo de Murciélagos en la Etapa de Ejecución de las Obras de Ampliación del EPF Floreña, Yopal, Casanare. 65 records from An updated checklist of aquatic plants of Myanmar and Thailand. 15554 records from A practical introduction to microbial molecular ecology through the use of iChips. 1 records from First record of Nesomesochorinae (Hymenoptera: Ichneumonidae) from America north of Mexico with descriptions of two new species of Nonnus Cresson. 4629 records from Ethnobotanical surveys species in Benin (West Africa). 10 records from Hidden gems in museum cabinets: new species and new distributional records of Scolytodes (Coleoptera: Scolytinae). 5576 records from uncultured prokaryote Targeted loci environmental. 2 records from Two new species of Garreta Janssens, 1940 (Coleoptera: Scarabaeidae: Scarabaeinae) from Southern Africa. 136 records from Inventaire faunistique de l'ENS des Parc des berges de Seine. 4174 records from Overvåking av åpen grunnlendt kalkmark i Oslofjordområdet. 133 records from Collection de longicornes et autres coléoptères saproxyliques de Lionel Valladares. 27 records from Additions to Andiorrhinus (Turedrilus) (Rhinodrilidae, Clitellata) from Eastern Amazonia. 1014 records from Soil invertebrates occurrences in European North-East of Russia. 51118 records from Queensland Museum provider for OZCAM. 2 records from A taxonomic reappraisal of the Smooth Slug Snake Asthenodipsas laevis (Boie, 1827) (Squamata: Pareidae) in Borneo with the description of two new species. 18620 records from Herbarium Universitatis Daugavpiliensis. 6387 records from Données naturalistes de Monsieur LAFAGE Denis. 113 records from Universidad del Valle de Guatemala - Colección de Artrópodos (UVGC). 5 records from On the genera Ptiloneura Enderlein, Loneura Navás, and Loneuroides García Aldrete (Psocodea: ‘ Psocoptera’: Ptiloneuridae). 4 records from IPAE egg clutches collection (Aves). 2208 records from marine sediment metagenome Raw sequence reads. 1 records from Review of the Madagascan Orphninae (Coleoptera: Scarabaeidae) with a revision of the genus Triodontus Westwood. 1 records from Molche in Ruschwedel. 708 records from EDP Baixo Sabor: Herpetology – Baseline Studies [2009]. 1 records from Redescription of two species and five new species of Dispio Hartman, 1951 (Spionidae: Polychaeta) from the eastern Pacific Coast and Caribbean Sea, with a review of the genus. 13 records from A review of the bats (Chiroptera) of the Republic of Congo, including eight species new to the country. 565 records from Colección Zoológica Universidad del Tolima (CZUT) - Arácnidos. 1989 records from Données d'observations d'orthoptères en Auvergne, d'Emmanuel Boitier, de 1998 à 2015.. 5 records from Two new records and one new species of the genus Apelaunothrips from China (Thysanoptera: Phlaeothripidae). 971 records from Vascular Plants from Praia da Vitória (Terceira, Azores, Portugal). 151 records from Análisis de las relaciones entre las diversidades alfa, beta y gamma a distintos niveles de escala espacial: Procesos históricos y ecológicos que intervienen. V Etapa. 1 records from A new Physoschistura from a Salween affluent in western Yunnan (Teleostei: Nemacheilidae). 1848 records from Plecoptera. 15 records from New and poorly known Holarctic species of Boletina Staeger, 1840 (Diptera, Mycetophilidae). 5 records from New species of Protosticta Selys from Vietnam with a key to the males of the P. curiosa group (Odonata: Platystictidae). 700 records from Données naturalistes d'Arnaud LE NEVÉ. 374 records from University of Amsterdam (NL) - Páramo Vegetation Research, National Natural Park El Cocuy, Colombia. 6 records from A review of Solierella Spinola, 1851 (Hymenoptera, Crabronidae) from Iran with description of four new species. 6 records from New Brazilian Tafaliscina increase the diversity of this Neotropical cricket clade (Orthoptera: Grylloidea: Gryllidae: Oecanthinae: Paroecanthini). 82 records from New taxa and records of Gryllacrididae (Orthoptera, Stenopelmatoidea) from South East Asia and New Guinea with a key to the genera. 5 records from New findings on the Neotropical species Hermetia goncalvensi Albuquerque, 1955 (Diptera: Stratiomyidae): redescription, puparium, and geographical records. 5818 records from Zomerganzen - Summering geese management and population counts in Flanders, Belgium. 68 records from Bees in the UVM Zadock Thompson Zoological Collection. 8 records from NZCS Brownsberg Nature Park Monitoring. 717 records from Redland City Council Citizen Science Portal. 15 records from Hessen-GEO-Tag am Schlossberg von Homberg/Efze. 248 records from HBRG Invasive Non-native Plants Dataset. 239 records from Caracterización de algas y comunidad íctica de la Isla Cayo Serrana durante la Expedición Seaflower 2016 - Proyecto Colombia BIO. 1 records from New species, new records, and new collection data of Rhyacophila from China (Trichoptera: Rhyacophilidae). 39672 records from North East Scotland Terrestrial Mammals 1900-2017 (excluding squirrels, wild cats and marine mammals). 52 records from EDP Foz-Tua: Riparian Birds (point counts) Ecological Monitoring Program [2011]. 166 records from Steinbruch Mainz-Weisenau, 3. Jahr. 34 records from NZCS Nassau Mountain Expeditions 2005/2006/2010/2014. 13 records from On the genus Systaria (Araneae: Clubionidae) in Southeast Asia: new species from caves and forests. 619 records from Museu Paraense Emílio Goeldi - Carcinológica Collection. 220 records from Inventario de sanguijuelas (Annelida: Clitellata Hirudinea) de México, con énfasis en las especies del centro de México. 2 records from Huangilene, a new genus for the Miltochrista alikangiae (Strand, 1917) species-group, with descriptions of three new species from Indochina, continental China and Taiwan (Lepidoptera: Erebidae: Arctiinae: Lithosiini). 2973 records from Réseau de surveillance Polynesia Mana - Peuplements de poissons. 7 records from Review of the genus Amemboides Polhemus & Andersen, 1984 (Hemiptera: Heteroptera: Gerridae) from China, with description of a new species. 2 records from Cnemaspis rajakarunai sp. nov., a rock dwelling day-gecko (Sauria: Gekkonidae: Cnemaspis) from Salgala, an unprotected lowland rainforest in Sri Lanka. 61 records from Naturpark Kottenforst-Ville 15.6.09. 1 records from Madangella altirostris, a new genus and species of palaemonid shrimps (Crustacea: Decapoda: Palaemonidae) from Papua New Guinea. 1031 records from ConDidact Citizen Science Surveys - Spiders 2011. 1087 records from Tree species composition of natural forest islands in a savanna matrix in the northern Brazilian Amazonia. 7 records from Lepidepecreoides stoddartae sp. nov. from the Falkland Islands (Amphipoda: Tryphosidae). 218 records from Land and freshwater molluscs of Northern Spain. 1812 records from The Belgica 121 expedition to the Western Antarctic Peninsula: a high resolution biodiversity census. 3407 records from Données naturalistes de Charlotte PICARD. 2 records from The genus Sinodiaptera Dellacasa (Coleoptera: Scarabaeidae: Aphodiinae) in Taiwan. 2 records from Euhampsonia rubricata spec. nov., a new moth species from northeastern India and western Myanmar (Lepidoptera: Notodontidae). 304 records from University of Nebraska State Museum Birds Collection. 173 records from FFH-Gebiet Klosterwasser/Burkau. 14 records from BCCM/ULC Cyanobacteria culture collection at the University of Liège (ISO9001 certified). 7 records from A new species of poison-dart frog (Anura: Dendrobatidae) from Manu province, Amazon region of southeastern Peru, with notes on its natural history, bioacoustics, phylogenetics, and recommended conservation status. 18812 records from University of California Santa Barbara Invertebrate Zoology Collection. 353 records from Données naturalistes de Hubert GUIMIER. 1219 records from Données naturalistes de Hervé BOUYON. 575 records from Données de la collection Rousset -1947-2013. 2 records from Revision of the genus Systellapha Enderlein (Micropezidae, Taeniapterinae). 1 records from The Shiny Cowbird, Molothrus bonariensis (Gmelin, 1789) (Aves: Icteridae), at 2,800 m asl in Quito, Ecuador. 76 records from Données du/de la naturaliste D'HINZELIN MARCEL provenant de la base de donnée du SINP Île-de-France CETTIA. 10 records from Ten new species of the spider genus Pholcus Walckenaer, 1805 (Araneae, Pholcidae) from Southeast Asia. 2 records from Vietnamella chebalingensis, a new species of the family Vietnamellidae (Ephemeroptera) from China based on morphological and molecular data. 386 records from Thistle Heads and Ermerged Insects. 57 records from CSIRO Yellow Box Fragmentation Project. 54 records from Review of some species groups of the genus Oospila Warren, with descriptions of nine new species (Lepidoptera: Geometridae: Geometrinae). 2968 records from Entomology Collection at the Natural History Museum of Utah. 874 records from Colección de Fabales del Museo Botánico CORD - IMBIV. 12094 records from Amino acid addition experiment Metagenome. 2 records from Morphological and molecular characterization of Klossnema viguerasi n. sp (Nematoda: Oxyuridomorpha: Hystrignathidae) from a Cuban passalid beetle (Coleoptera: Passalidae), first record of the genus for Cuba. 3131 records from Données DREAL Centre-Val de Loire - Faune - 2018. 36676 records from ALCB - Herbário Alexandre Leal Costa. 55 records from Vegetationsmatrix schorfheide alb 2008 durchgang2. 114 records from BIRDRACE LiLaLau. 3560 records from Biobanco de ADN Vegetal de la Universidad de Salamanca: SALA-DNA. 65759 records from Fish specimens of Kagoshima University Museum. 46266 records from Tetraonid line transect surveys from Norway: Data from Fjellstyrene. 14 records from UTEP Invertebrates (Arctos). 24 records from Revision of the crab-spiders of the genus Runcinioides Mello-Leitão, 1929 (Araneae, Thomisidae). 1288 records from Comparative metagenome analysis of normal and arsenic contaminated soils from ballia district, Uttar Pradesh, India. 10 records from A new genus of ground and litter-dwelling pholcine spiders from Sarawak (Araneae, Pholcidae). 684 records from Inventario de Flora de la Reserva Forestal Protectora Regional Cuchillas del Tigre, El Calón y La Osa. Municipios de San Francisco y Sonsón-Antioquia.. 8 records from Electrogena brulini sp. nov. and E. vipavensis Zurwerra & Tomka, 1986 syn. nov. revealed by integrative taxonomy of E. gridellii (Grandi, 1953) (Ephemeroptera: Heptageniidae). 7 records from Revision of the genus Cobbionema Filipjev, 1922 (Nematoda, Chromadorida, Selachinematidae). 292 records from Monitoreo y recolección de la diversidad de razas de maíz criollo en la región de la Huasteca en México para complementar las colecciones de los Bancos de germoplasma de INIFAP y CIMMYT. 9002 records from Uncultured Environmental Isolate Targeted loci environmental. 145 records from Fototrampeo al interior de las áreas del Banco de Hábitat del Meta de Terrasos. 258354 records from MGYS00005313. 2 records from Two new species of the genus Sinodorcadion Gressitt, 1939 (Coleoptera: Cerambycidae: Lamiinae). 1131 records from eDNA_Subseafloor. 1127 records from marine sediment metagenome Metagenome. 61 records from Inventario de vertebrados nativos en las islas Guadalupe, San Benito, Natividad, Asunción, San Roque, Isabel, Marietas, Socorro, Banco Chinchorro y Arrecife Alacranes (Crustáceos). 634 records from Colección de macroalgas de la costa Argentina (IADO-UNS-CONICET). 3752 records from Microbial ecology of archaeal community in sediment from adjacent waters of Rushan Bay. 8744 records from Invasive Plant Atlas of the MidSouth (IPAMS). 71 records from Invasive plants in Luronium natans habitats in Flanders, Belgium. 371 records from Bannwald Burghauser Forst. 1296 records from Códigos de barras de la vida en peces y zooplancton de México. 7 records from The publication of primary biological events in the international GBIF (Global Biodiversity Information Facility) network: A case study with a small dataset of field collected occurrence samples of Buriti palms (Mauritia flexuosa).. 2 records from Tertiarius minutulus sp. nov. (Stephanodiscaceae, Bacillariophyta) - a new fossil diatom species from Lake Ohrid. 16330 records from SEWBReC Bees, Wasps and Ants (South East Wales). 290 records from Données 2016 Pélobate brun Comité Départemental de Protection de la Nature et de l'Environnement. 5568 records from Fitoplancton de la provincia oceánica del mar Caribe colombiano. Diez años de historia. 2 records from Two new species of Dentilabus Heinrich (Hymenoptera: Ichneumonidae: Ichneumoninae) from Japan and Korea, with redefinition of the genus. 5 records from Revision of the genus Parvimysis (Mysida, Mysidae) with descriptions of five new species from coastal waters of the Caribbean. 1 records from A new species of Casmaria H. Adams & A. Adams, 1853 (Gastropoda, Cassidae) from the Philippines identified by molecular data. 10 records from The genus Mecodema Blanchard 1853 (Coleoptera: Carabidae: Broscini) from the North Island, New Zealand. 1 records from Revision of Lutnes Cameron (Hymenoptera: Eupelmidae). 391 records from ZUEC-OPH - Coleção de Ophiuroidea do Museu de Zoologia da UNICAMP. 20 records from Meiofauna densities from in situ feeding experiments in the Nazare Canyon conducted with sediments from ROV push-core JC10-95-PUC03. 154 records from Sorensen distance for herbivores. 89 records from Great British Bee Count 2016 - Stage 2 (records verified from photo). 14 records from Chronicle of Nature - Phenology of Insects of National Park Bashkirija. 752 records from University of Guam Insect Collection. 833 records from Plant species from the sacred and community forests of Mono departement. 24412 records from KTP Ring Data. 580 records from Colección Ornitológica-Museo de Historia Natural Unillanos. 174 records from Artenvielfalt des "Grünen Klassenzimmers". 2 records from Two new species in the genus Indolipa Emeljanov, 2001 (Hemiptera: Fulgoromorpha: Cixiidae: Pentastirini) from China. 3 records from Pseudotibiozus Demange, 1970 - millipedes of the Eastern Arc Mountains, Tanzania (Diplopoda, Spirostreptida, Spirostreptidae). 11 records from Données d'observation opportunistes collectées durant la campagne de prélèvements sédimentaires SHELL/CREOCEAN en Guyane française en 2013. Shell Exploration and Production France. 777 records from Arbeitsgemeinschaft Heuschrecken Österreichs. 16 records from Subspecies of Pleurota bicostella (Clerck, 1759) revisited and descriptions of nine new species in the P. bicostella species group (Lepidoptera: Gelechioidea Oecophoridae: Pleurotinae). 440 records from Zoocenosis of the mole burrows in the forest zone of Western Siberia. 443 records from Museu de Ciències Naturals de Barcelona: BGJBB. 1422 records from Australian Institute of Marine Science (AIMS) - Lizard Island Reef Biodiversity Expedition, Queensland, Australia (2008 - 2009). 1 records from Two new genera and species of Fidicinini Distant, 1905 with a re-description of Nosola Stål, 1866 (Hemiptera, Auchenorrhyncha, Cicadidae). 12118 records from Soil metagenome from healthy and unhealthy agricultural soil. 2 records from A new species of Ahaetulla Link, 1807 (Serpentes: Colubridae: Ahaetullinae) from India. 2 records from New state and island records of Coccinellidae (Coleoptera) in Hawai‘i, USA. 10573 records from Inventario florístico y entomofaunístico en tres objetos de conservación ecosistémicos en las zonas núcleo de las reservas estatales de Balam-kú y Balam-kin, Campeche (Plantas). 3 records from Holomorphology of Kamimuria peppapiggia sp. n. (Plecoptera: Perlidae) from the foothills of Taihang Mountains, Henan Province of China. 1 records from A new species of Synopeas (Hymenoptera: Platygastridae) parasitizing Pauropsylla cf. depressa (Psylloidea: Triozidae) in India. 1 records from Three new species of the free-living marine nematode Metoncholaimus Filipjev 1918 (Enoplida, Oncholaimidae) from Argentinean coasts. 1 records from Brown University Herbarium. 520 records from UWIZM Molluscs. 89 records from Données du/de la naturaliste Le baron Gaetan provenant de la base de donnée du SINP Île-de-France CETTIA. 875 records from Caracterización biológica de la ventana de biodiversidad Montes de María, Municipio de Colosó, Sucre, Colombia. 95 records from BIRDRACE accipiter hardcore birding. 19317 records from Inventaire de la flore des Pyrénées-Atlantiques 2017 - Littoral. 318 records from Marine Mammal Observation - Total E&P Angola 2006-2011. 2799 records from MCP-Aves - Coleção de Aves. 10 records from A revision of Eastern Palaearctic Anthobium Leach, 1819 (Coleoptera: Staphylinidae: Omaliinae: Anthophagini). II. fusculum group, and two additional species of the nigrum group. 11 records from The millipede genus Glomeris Latreille, 1802 (Diplopoda, Glomerida, Glomeridae) in North Africa. 2 records from Danio htamanthinus (Teleostei: Cyprinidae), a new species of miniature cyprinid fish from the Chindwin River in Myanmar. 652 records from POPA- Fisheries Observer Program of the Azores: Discards in the Azores tuna fishery from 1998 to 2013. 5 records from Bird specimens of Saitama Museum of Natural History. 17 records from orthopteracollections-nhmj-ioj. 1 records from Redescription of Platynaspis flavoguttata (Gorham) (Coleoptera, Coccinellidae) and notes on nomenclature of Platynaspis kapuri Chakraborty & Biswas. 2 records from A new species of Cyrtodactylus (Squamata: Gekkonidae) and the first record of C. otai from Son La Province, Vietnam. 2 records from Description and phylogenetic relationships of a new trans-Andean species of Elachistocleis Parker 1927 (Amphibia, Anura, Microhylidae). 1065 records from Interannual variability of ichthyoplankton diversity in the Patos Lagoon estuary Southern Brazil. 10703 records from Collections of Bioclass, school #179, Moscow. 6 records from Two new species of the conger eel genus Bathycongrus (Anguilliformes: Congridae) from Taiwan. 14 records from RNF - Données de la Réserve Naturelle du Marais de Lavours. 9 records from Amazoonops, a new genus of goblin spiders (Araneae: Oonopidae) from the Brazilian Amazon. 2 records from Porphyrocrinus daniellalevyae n. sp. (Echinodermata: Crinoidea), a sea lily from the tropical western Atlantic with a unique crown pattern. 988 records from flower availability 2008 Alb-korrigiert. 14576 records from Inventario de flora, avifauna, mamíferos, mariposas y peces realizado en el sector de Puerto Abeja y durante la expedición científica en la ventana Mesay en el sector sur del Parque Nacional Natural Serranía de Chiribiquete. 2 records from A new ant species of the Leptogenys sulcinodagroup (Hymenoptera: Formicidae) from Saudi Arabia. 30 records from Revision of the Ephippiochthonius complex in the Iberian Peninsula, Balearic Islands and Macaronesia, with proposed changes to the status of the Chthonius subgenera (Pseudoscorpiones, Chthoniidae). 42 records from Inventaire des Octocoralliaires des fonds sédimentaires de la région niçoise. 1477 records from Inventaire des espèces végétales productives dans les Systèmes Agro-forestiers aux alentours de la Forêt classée de Ziama en Guinée Forestière (BID-AF2015-0066-REG). 6 records from A new species of the genus Bertholdia Schaus, 1896 (Lepidoptera: Erebidae: Arctiinae) from the Neotropical region: Bertholdia zoenia sp. n.. 7 records from The millipede genus Tylopus Jeekel, 1968 (Diplopoda, Polydesmida, Paradoxosomatidae), with a key and descriptions of eight new species from Indochina. 3 records from Revision of the Australian Union-Jack wolf spiders, genus Tasmanicosa (Araneae, Lycosidae, Lycosinae). 11498 records from Digitalización y sistematización de las colecciones biológicas del INECOL (Herbario). 31 records from New distribution data for some charismatic tramp species of Platygastroidea (Hymenoptera). 2804 records from Coral Reef Evaluation and Monitoring Project Florida Keys 2015. 2 records from A new species of Rhabdops Boulenger, 1893 (Serpentes: Natricinae) from the northern Western Ghats region of India. 1 records from Stylogomphus thongphaphumensis (Odonata: Anisoptera: Gomphidae), a new gomphid dragonfly and the first record of S. malayanus Sasamoto, 2001 from Thailand. 4 records from Discovery of the genus Kudakrumia Krombein, 1979 (Hymenoptera: Mutillidae) in India and description of a new species. 22771 records from INVESTIGATING THE MICROBIAL EUKARYOTIC COMMUNITIES IN THE SURFACE WATERS OF THE ARAFURA SEA AND CORAL SEA. 1824 records from TransForest - vegetation, lichen and fungi data 2016. 3 records from Otacilia fansipan spec. nov., the second congener recorded from Vietnam (Arachnida: Araneae: Phrurolithidae). 29 records from UWIZM Anoles. 2 records from Three new species of Cladorhiza (Demospongiae, Poecilosclerida, Cladorhizidae) from the Northeast Pacific Ocean. 588 records from artsprosjektet_51-14_ophiostomatoid_fungi. 146 records from Registros de la vegetación presente en la Cienaga de Beté, Municipio del Medio Atrato, Chocó - 2018. 5 records from New species and new geographical record of Ochrotrichia Mosely 1934 (Trichoptera: Hydroptilidae) from Rio de Janeiro state, Brazil. 10776 records from CEFS_16S_ITS. 36323 records from Biowide Species data. 9 records from Inventaire et regroupement de données Natura 2000. 2179 records from RNF - Données du Parc Naturel Régional du Vercors. 28 records from Registros de Lepidoblepharis miyatai (Gecko enano) en la costa Caribe Colombiana. 1441 records from POPA- Fisheries Observer Program of the Azores: Turtle sightings in the Azores tuna fishery from 2000 on: during navigation or search mode.. 876 records from Ensemble des données Odonates. 49 records from Family Geraniaceae in CSBG SB RAS herbarium collections (NS, NSK). 168 records from Diversité et distribution de quelques espèces de plantes agroforestières au Bénin. 1 records from First description of the male of the type species Meotipa picturata Simon, 1895 and description of a new Meotipa species (Araneae, Theridiidae) from India. 572 records from The hoverfly collection (Diptera, Syrphidae) of the International Institute of Tropical Agriculture (IITA) at Calavi (Benin). 7 records from Taxonomic revision of Ceropegia sect. Huernia (Asclepiadoideae, Apocynaceae) in Saudi Arabia with three new combinations. 20 records from Description of five new Wulfila (Araneae, Anyphaenidae) species from Mexico with comments on the taxonomy of the genus. 4 records from A new South American species of Banasa Stål (Hemiptera: Heteroptera: Pentatomidae: Pentatominae): from egg to adult. 2526 records from sea water Picoeukaryotic Community Raw sequence reads Raw sequence reads. 32 records from IOW Natural History & Archaeological Society Marine Records. 13 records from A new species of Leptolalax (Anura: Megophryidae) from northern Vietnam. 323 records from Modelos predictivos de distribución geográfica para Spizella wortheni, Cynomys mexicanus, Vulpes macrotis zinseri y Taxidea taxus berlandieri. 6 records from Records of pine martens from SNH casework reports and licence applications, 2005 - 2016. 6189 records from Fauna y flora en áreas con cultivos de palma de aceite en el norte y oriente de Colombia. 71 records from Bringing Reedbeds to Life Water Vole and Mink Survey of five key reedbed sites in England in 2009, 2010. 1422 records from Données du/de la naturaliste Chevreau David provenant de la base de donnée du SINP Île-de-France CETTIA. 21 records from Base de datos de las especies maderables del género Dalbergia en México, registros del Herbario Nacional de México (MEXU). 2095 records from Communauté_de_communes_Asse_Bléone_Verdon_2017_12_18. 10389 records from Seawater metagenome Targeted loci environmental. 2 records from A new species and two new records of the ground spider genus Apopyllus (Araneae, Gnaphosidae) from Paraguay. 12 records from Art´n Vielfalt im Kinderwald. 41 records from Asturodes Amsel (Lepidoptera: Crambidae: Spilomelinae): Three New Species From The Western Hemisphere And Food Plant Records From Area De Conservación Guanacaste, Costa Rica. 135 records from Waldi-Weiher. 50 records from Herpetofauna de la expedición Pisba - Proyecto Boyacá BIO UPTC. 13 records from Taxonomic study of the genus Fujimacia Marumo, 1939 (Lepidoptera: Pyralidae) in China, with descriptions of four new species. 491 records from Invasive Non-Native Species, Outer Hebrides. 180 records from Naturalis Biodiversity Center (NL) - Crustacea. 607 records from Inventory of Bassila forest (North-Benin). 3 records from A new species, a new combination, and a new record of Crossotarsus Chapuis, 1865 (Coleoptera, Curculionidae, Platypodinae) from China. 6440 records from Microbial ecology of bacteiral community in sediment from adjacent waters of Rushan Bay. 414 records from Georgia Southern University - Savannah Science Museum Herpetology Collection. 680532 records from CLICNAT Base de données naturaliste picarde gérée par Picardie Nature. 237168 records from Leicestershire and Rutland Environmental Records Centre records 2015-2019. 645 records from Molluscs in surface sediments off Sylt collected during HEINCKE cruise HE293. 29903 records from DATAVES. 1 records from Revision of Terellia amberboae group of species (Diptera: Tephritidae). 2572 records from seawater metagenome Metagenome. 23 records from Herpetofauna asociada a la cuenca del río Quito - Chocó, 2014. 296 records from DATABASE OF FINDS OF RARE LICHEN SPECIES Lobaria pulmonaria IN RUSSIA. 2 records from Taxonomic Studies on the Genus Myrmoteras Forel (Hymenoptera: Formicidae), with Description of Two New Species from India. 3752 records from (Appendix 8) Distribution of barnacles, bivalves, gastropods, and calcified worm tubes in sediment samples collected between 1995 and 2010 in the San Francisco Bay coastal system. 1917 records from Diet results from Adelie penguins at Bechervaise Island and Whitney Point, 2012/13. 1574 records from Heliconiine Butterfly Collection Records from University of Cambridge. 213 records from The Broward College Insect Collection. 156 records from SNH Invertebrate Site Condition Monitoring 2013/14: Earlshall Muir SSSI. 1468 records from Colección Regional de Equinodermos de la Peninsula de Yucatan. 2 records from A New Southern Caribbean Species of Angel Shark (Chondrichthyes, Squaliformes, Squatinidae), Including Phylogeny and Tempo of Diversification of American Species. 14 records from Berea College, Ralph L. Thompson Herbarium. 31 records from Macrohongos de los bosques montanos del Oriente Antioqueño, Cañón del río Melcocho, en el municipio de El Carmen de Viboral, Antioquia - Proyecto Colombia BIO. 4 records from Determinación de la clase Reptilia presente en el corregimiento de Juanchaco, Valle del Cauca, Colombia para el mes de Septiembre de 2017. 355 records from (Table 2) Species density and composition of an inshore and offshore station in Kongsfjord, Svalbard. 255 records from Tejidos colectados en el páramo de Pisba, Boyacá - Proyecto Boyacá BIO. 41 records from NEON Biorepository Zooplankton Collection (DNA Extracts). 79 records from Birdrace-Bielefinken-Bielefeld. 9653 records from Ecosphère_2017_12_18. 2619 records from Kenai National Wildlife Refuge, Alaska (KNWR) Insect specimens (Arctos). 107 records from Müritz-Nationalpark. 642 records from Análisis de la biodiversidad y servicios ecosistémicos para su aplicación en la toma de decisiones en el departamento de Boyacá/Boyacá Bio-Flora El Consuelo. 70 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-2. 8 records from First records of two flower bug genera from Myanmar (Hemiptera: Heteroptera: Anthocoridae: Anthocorinae: Oriini), with description of a new species of Bilia. 5708 records from Colección Limnológica Universidad de Antioquia. 378 records from Rock ptarmigan (Lagopus muta) radio telemetry in Lierne, Norway. 146 records from Birdrace-Wannacks_Topti(c)ker-Lübeck. 22520 records from Fermanagh Flora. 502 records from Museo Provincial de Ciencias Naturales “Dr. Ángel Gallardo”, Rosario, Argentina - Colección Peces (MG-ZV-P). 11774 records from Tachinid Recording Scheme - Tachinid fly records verified via iRecord. 6767 records from VIES herbarium - Universidade Federal do Espírito Santo - Herbário Virtual REFLORA. 680543 records from Bryophyte data for Great Britain from the British Bryological Society held by BRC: Atlas 2014. 1 records from Description of a new species of the Melanorivulus pictus species-group (Cyprinodontiformes: Rivulidae) from the Rio Paraná basin in Brazil. 2 records from Baetis pentaphyllus sp. nov., a new species of mayfly (Ephemeroptera: Baetidae) from the Russian Far East. 4863 records from NRW Regional Data: South East Wales Non-sensitive species. 2 records from Gyrinus rhyssonotum sp. n., a new species of Gyrinidae (Coleoptera: Adephaga) from northern Brazil. 294 records from Aves de la expedición en el páramo El Valle, Boyacá - Proyecto Boyacá BIO. 1 records from A New Species Of Novius Mulsant From New Caledonia (Coleoptera: Coccinellidae: Noviini). 1 records from Phasmatodea Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 372 records from Recursos hidrobiológicos de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 1 records from Taxonomic review of the genus Compsiluroides Mesnil (Diptera: Tachinidae), with the description of a new species. 5 records from Three new country records from the genus Limnephilus Leach, 1815 (Trichoptera: Limnephilidae) from the Republic of Kosovo. 86 records from CEPEC herbarium - Centro de Pesquisas do Cacau - Herbário Virtual REFLORA. 5 records from Cave-inhabiting Neobisiidae (Arachnida: Pseudoscorpiones) from China, with description of four new species of Bisetocreagris Ćurčić. 5 records from Taxonomic changes of some neotropical species of Arctiini Leach (Lepidoptera: Erebidae: Arctiinae). 1 records from A new species of Creagrutus (Characidae: Stevardiinae) from the upper Río Magdalena, Colombia. 4616 records from Inventaire de la flore du Grand Poitiers 2009. 33 records from Waldstück am Schullandheim Bad Bederkesa. 10 records from Review of Anasillomos Londt, 1983 with the description of a new species (Insecta : Diptera : Asilidae). 74 records from Anfibiofauna asociada a la quebrada Giginia, corregimiento de Doña Josefa, Municipio del Atrato - Chocó, 2019. 334 records from Aves de la expedición en el páramo de Bijagual, Boyacá - Proyecto Boyacá BIO. 3150 records from Collembola of Karelia: multiscale analysis of spatial distribution in pine forests. 1 records from Données naturalistes d'Olivier DELZONS. 140 records from Naturalis Biodiversity Center (NL) - Diptera. 37 records from FBIP: scallop population genetics. 18 records from Schulgarten der Gesamtschule Am Heidberg. 72 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-11. 1 records from A new species of Aphonopelma (Araneae: Mygalomorphae: Theraphosidae) from the Madrean pine-oak woodlands of northeastern Sonora, Mexico. 78 records from Museu Paraense Emílio Goeldi - Opiliones Collection. 11 records from New species of Condylostylus Bigot (Diptera: Dolichopodidae) from Comoros Madagascar, Tanzania and South Africa, with key to Afrotropical species. 1270 records from Données du/de la naturaliste Lantz André provenant de la base de donnée du SINP Île-de-France CETTIA. 2 records from The genus Synergus Hartig (Hymenoptera: Cynipidae: Synergini) in the New World: a complete taxonomic revision with a key to species. 25 records from Read between the lineata: A revision of the tattooed wasps, Zagrammosoma Ashmead (Hymenoptera: Eulophidae), with descriptions of eleven new species. 70 records from Gewässer des Wartbergparks Stuttgart (bei der Ökostation der VHS Stuttgart). 5 records from Inventur der Natur rund ums NABU-Naturzentrum in Haseldorf. 1 records from Society Islands beach bum black flies (Diptera: Simuliidae). 6 records from Epinephelus fuscomarginatus (Perciformes: Epinephelidae), a new species of grouper from off the Great Barrier Reef, Australia. 174 records from BIRDRACE Bon(n)apartemöwen. 538 records from Composición florística y estructura de una parcela permanente en bosques húmedos tropicales del municipio de Pie de Pepe, Chocó. 7 records from Plant-parasitic nematodes of Republic of Karelia. 22 records from Computarización de material complementario en la Colección Regional de Invertebrados del Pacífico mexicano, Instituto de Ciencias del Mar y Limnología, Unidad Académica Mazatlán, UNAM. 1545 records from NatureMap Calcrete Survey. 62 records from Données naturalistes de BONCHE Jérôme. 4183 records from Marine Bird Sighting Data, Arctic Marine Biodiversity Observing Network (AMBON) Chukchi Sea research cruise on the vessel Norseman II from 2015-08-09 to 2015-09-03. 32 records from Abyssal fauna of the UK-1 polymetallic nodule exploration claim, Clarion-Clipperton Zone, central Pacific Ocean: Echinodermata. 125 records from Universidad de Murcia, Dpto. Biología Vegetal (Botánica), Murcia: MUB-MUSCI. 9 records from Character state variation within Dendrothrips (Thysanoptera: Thripidae) with a revision of the species from China. 5 records from Biodiversity of spider mites (Acari: Tetranychidae) in Serbia: a review, new records and key to all known species. 1413 records from Hormigas del Museo de Entomología de la Universidad del Valle. 2465 records from Elaboration de table de tarif de cubage multispécifique (I). 1 records from Reptiles Specimens of Akita Prefectural Museum. 120 records from BIRDRACE The early birds. 1 records from A new species of Neoscelis Schoch from Mexico (Coleoptera: Scarabaeidae: Cetoniinae: Goliathini) with new distributional records for the genus. 1417 records from Données odonates collectées par le CEN Aquitaine entre 1995 et 2015. 2806 records from University of Michigan Museum of Zoology, Division of Reptiles & Amphibians. 229 records from Queen Charlotte Sound / Tōtaranui and Tory Channel / Kura Te Au (HS51) Hydrographic Survey Marine Mammal Observations. 445 records from RECORD Orthoptera Data. 50076 records from DFO Pacific Outside South Hard Bottom Longline Surveys. 3 records from New species of Graphocaecilius Enderlein (Psocodea: ‘ Psocoptera’: Lachesillidae) from Colombia. 4 records from Two new species of Guyruita Guadanucci et al., 2007 (Araneae, Theraphosidae) from Brazil. 7 records from A checklist of epibiont suctorian and peritrich ciliates (Ciliophora) on halacarid and hydrachnid mites (Acari: Halacaridae & Hydrachnidia). 92 records from Protozoa Abundance_Microbial Parameters. 1 records from A new species of Polyipnus (Stomiiformes: Sternoptychidae) from the Western South Pacific. 17 records from New species of Pyrrhulina (Teleostei: Characiformes: Lebiasinidae) from the eastern Amazon, Pará, Brazil. 718 records from Bird species occurrences recorded from selected sites in mid Tana River Basin, Kenya. 368 records from Données du naturaliste PROVOST romain provenant de la base de donnée du SINP Île-de-France CETTIA. 13545 records from Temporal dynamics of bacterioplankton community in response to excessive nitrate loading in the oligotrophic coastal water. 93 records from Wildlife Sightings in the City of Logan. 31 records from Birds Specimens. 3 records from Demoulinia Gillies 1990 and two unnamed genera of the plesiomorphon Protopatellata (Ephemeroptera, Baetidae) from South Africa. 94 records from Suivi de l'expansion du Frelon asiatique (Vespa velutina) : données espèces non cibles piégées. 592 records from Caracterización de Fauna del Banco de Hábitat del Bosque Seco Tropical Antioquia de Terrasos. 1 records from A revision of the Anthaxia (Anthaxia) midas Kiesenwetter, 1857 species-group (Coleoptera: Buprestidae: Anthaxiini). 1710 records from Herpetofauna de la región marina prioritaria Corredor Puerto Madero, Chiapas, México. 537 records from Upper Silesian Museum, Bird Observations. 86 records from Fliegenhaupt Marksuhl. 25 records from The genusParascepsis Dognin, 1923 (Lepidoptera, Erebidae, Arctiinae, Ctenuchina) in Peru, with the description of three new species, a new combination and their geographical distributions. 9036 records from DMNS Mammal Collection (Arctos). 1046 records from Données naturalistes de Quentin ROME. 624 records from Back from the Brink vascular plant species abundance and distribution for Great Britain for the period 2002-2009. 1 records from A new species of the genus Pachytriton (Caudata: Salamandridae) from Hunan and Guangxi, southeastern China. 182 records from SEWBReC Springtails and allies (South East Wales). 6 records from Four new species of Phrynus, Lamarck (Arachnida: Amblypygi) from Mexico. 1 records from Culicoides Latreille biting midges (Diptera: Ceratopogonidae) of the Dongzhaigang mangrove forest, Hainan Province, China. 855 records from Insectos recolectados en trampas Malaise en el departamento de Santander - Proyecto Colombia Bio. 35 records from Taxonomic review of the ladybird genus Sticholotis from China (Coleoptera: Coccinellidae). 64 records from Bats of northeastern Vietnam. 1028 records from IBF Monitoring of Fungi. 437 records from The Himalayan Uplands Plant database (HUP Version 1). 131 records from Artenvielfalt auf dem Schulgelände. 4 records from Phylogenetic differentiation and taxonomic consequences in the Saurodactylus brosseti species complex (Squamata: Sphaerodactylidae), with description of four new species. 370 records from Coral Reef Evaluation and Monitoring Project Dry Tortugas 2007. 1 records from A new species of Decomia Poppius from Laos and Thailand, with an annotated checklist and keys to genera and species of tribe Decomiini from Indochina (Hemiptera: Heteroptera: Miridae: Phylinae). 5 records from New data on jumping spiders of Iran, with a new species of Salticus (Araneae: Salticidae). 117 records from Programme de valorisation des zones humides chassées - volet Amphibiens. 179 records from National Museum of Natural Science. 179 records from A survey of the weevils of Ukraine (Coleoptera: Curculionoidea). 3018 records from Caracterización de flora, edafofauna epígea, anfibios y aves del Complejo de Páramos Pisba, Boyacá. 27 records from Caracterización floristica del Alto del Buey, Bahia Solano - Chocó. 11 records from New and little-known sun-moth species from Australia (Lepidoptera, Castniidae). 165 records from Diversidad de anfibios en tres coberturas vegetales y su relación con actividades antrópicas (amenazas) presentes en el Parque Nacional Natural Tatamá y su área de influencia.. 187 records from Agencement temporel des populations et des peuplements d'invertébrés benthiques. 1 records from Catalog of the Paramacronychiinae of China (Diptera: Sarcophagidae). 74 records from Seven new species of the spider genus Matta Crosby from caves in the State of Minas Gerais, Brazil (Araneae, Tetrablemmidae). 69 records from BIRDRACE Pfeifenten. 70 records from Données 2017 de l'Observatoire de la Biodiversité des Forêts. 25 records from Ephemeroptera Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 38 records from The Pygopleurus Motschulsky (Coleoptera: Scarabaeoidea: Glaphyridae) of mainland Greece: taxonomy, faunistics and ecological notes. 146 records from Données de la naturaliste Laurence Beauchamp. 1 records from Collections ichtyologiques et herpétologiques (BOUM). 82 records from MCP-Mamiferos - Coleção de Mamíferos. 3 records from A new madicolous species of Nilotanypus Kieffer (Diptera: Chironomidae) from Amazon region, northwestern Brazil. 8178 records from Données naturalistes de Bruno OGER. 208 records from Colección de mariposas del Museo de Entomología de la Universidad del Valle. 1 records from Ta xonomic study on the Chinese Steninae (Coleoptera, Staphylinidae), with descriptions of three new species of the Genus Stenus Latreille. 3 records from First record of the genus Tanaostigma (Hymenopteraı Chalcidoideaı Tanaostigmatidae) from the Afrotropical region with description of three new species. 358 records from Données du Syndicat de la Vallée de l'Orge Aval (SIVOA). 3 records from Five new species and novel descriptions of opposed sexes of four species of the spider genus Attacobius (Araneae: Corinnidae). 686 records from Expediciones en biodiversidad alrededor del Cacao en el marco del proyecto Colombia Bio. 1 records from A new deep-sea species of the caridean genus Bresilia Calman, 1896 (Crustacea: Decapoda: Bresiliidae) from Sagami Bay, central Japan. 1735 records from Occurrence database of native plants and animals of south-central Chile. 13 records from Three new species and three new records of the genus Bamboosiella from China (Thysanoptera: Phlaeothripidae). 82 records from Données du/de la naturaliste Swoszowski Florie provenant de la base de donnée du SINP Île-de-France CETTIA. 1 records from Sarcocheilichthys vittatus, a new species of gudgeon (Teleostei: Cyprinidae) from the Poyang Lake Basin in Jiangxi Province, South China. 1102 records from NE Scotland fish records 1800-2010. 259 records from Natura 2000 Parc naturel régional de Lorraine. 1 records from Nothobranchius nikiforovi, a new species of seasonal killifish from the lower Matandu drainage in south-eastern coastal Tanzania (Cyprinodontiformes Nothobranchiidae). 51267 records from Données de l'AFB acquises selon le protocole de pêche complète à un ou plusieurs passages. 3825 records from Census of the species of Benin. Data mobilized in the framework of JRS Benin project and funded by JRS Biodiversity Foundation. 2 records from Description of a new snake eel Ophichthus olivaceus (Teleostei: Anguilliformes Ophichthidae) from the Red Sea. 609 records from Arácnidos - Miriápodos de la expedición al Río Apaporis - Proyecto Colombia BIO. 4 records from Moriphila furva gen. and sp. nov. (Hemiptera: Psylloidea: Homotomidae), a new jumping plant-louse from Korea associated with Morus australis (Moraceae). 2 records from Aradidae from Vietnam V. Bifurcatoaptera, a new genus of apterous Carventinae (Hemiptera: Heteroptera: Aradidae) from Vietnam. 2 records from Hangzhou-sediment-sample Raw sequence reads. 1 records from The genus Zelurus Hahn, 1826, in Brazilian caves: description of new species and comments on the potential distribution of the genus in South America. 14 records from A new freshwater shrimp species of the genus Palaemon Weber, 1795 (Decapoda: Caridea: Palaemonidae) from northeastern Japan. 144 records from BIRDRACE Punkbirder Helgoland. 574 records from Conservación de la tortuga caguama del Pacífico (Caretta caretta): protección dentro del hábitat crítico de alimentación y desarrollo en Baja California Sur. 3 records from A new species of the greeneye genus Chlorophthalmus (Teleostei: Chlorophthalmidae) from the central North Pacific. 2 records from Campydoroides manautei gen. et sp. nov. from New Caledonia and a reappraisal of the suborder Campydorina (Nematoda). 5 records from Revision of Tomocerus similis Chen & Ma, with discussion of the kinoshitai complex and the distal tibiotarsal chaetae in Tomocerinae (Collembola, Tomoceridae). 6 records from Four new crane fly species of subgenus Tipula (Vestiplex) (Diptera, Tipulidae) from China. 243 records from Fish species occurrences from selected near shore and riverine habitats in Lake Edward (2019). 2 records from Small, rare and little known: new records and species of Cardiomya (Bivalvia: Cuspidariidae) from Brazil. 3 records from Two new Cyphoderus (Collembola: Paronellidae) of “ tridenticulati ” and “ bidenticulati ” groups from Brazilian Amazon. 87 records from Occurrences of Boeckella at high latitudes in the southern hemisphere. 143 records from UWIZM Snakes. 2 records from A new species of Rock Gecko genus Cnemaspis (Squamata: Gekkonidae) from Western Sarawak, Malaysia. 22 records from Wildgehege Glauer Tal (Naturpark Nuthe-Nieplitz). 23 records from Taxonomic revision of the Cis-Andean species of Mylossoma Eigenmann & Kennedy, 1903 (Teleostei: Characiformes: Serrasalmidae). 158 records from Planktonic foraminifer occurrences and zonations from IODP Hole 313-M0029A. 16 records from Insect Collections of Okomu National Park- Nigeria. 33792 records from University of Minnesota Insect Collection. 4538 records from ARABEL - Arachnologia Belgica. 412 records from Heinersdorfer Sumpfwiese. 8 records from The genus Asiagomphus in Vietnam, with descriptions of three new species, and first descriptions of the male of Asiagomphus auricolor (Fraser, 1926) and of the female of Asiagomphus reinhardti Kosterin & Yokoi, 2016 (Odonata: Gomphidae). 2112 records from Arctic Species Trend Index (ASTI) : Marine. 8473 records from Wolli Creek Preservation Society Bird Survey. 182 records from Tejidos colectados en el piedemonte llanero, Boyacá - Proyecto Boyacá BIO. 141 records from Biodiversity survey of Rugezi wetland, Year 2013. 63 records from Inventaire des espèces végétales de la vallée de Gounti Yéna (Niamey). 306 records from MLZ Bird Collection (Arctos). 449 records from Artsprosjekt Pyrenomycetes. 12 records from Leiocassis rudicula (Teleostei: Siluriformes: Bagridae), a new catfish from eastern Borneo. 4 records from Crustáceos del municipio Santa Bárbara, Santander - Proyecto Santander BIO. 6654 records from NOAA coral reef monitoring benthic data from sites across Micronesia from 2009-09-29 to 2015-09-25. 121 records from Etude écologique du Parc des Lilas (94). 10 records from The megadiverse fauna of Neotropical Cerambycidae (Coleoptera): Notes, descriptions, new records, new species, and revalidations. 69 records from PRESENCIA DE VISÓN AMERICANO EN TIERRA DEL FUEGO, MAGALLANES, CHILE. 1 records from New records and updated distribution of the ant-like jumping spider genus Zuniga Peckham & Peckham, 1892 (Salticidae: Salticinae: Sarindini) in the Neotropics. 11 records from Notes on the Dianous aereus complex with description of a new species (Coleoptera, Staphylinidae). 17 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-5. 2592 records from Coral Reef Evaluation and Monitoring Project Florida Keys 2018. 430 records from Archaeal diversity of surface seawater (A3,A5,G3,G5) Targeted Locus (Loci). 118 records from Birdrace-Birding_Bentheim-Grafschaft_Bentheim. 148143 records from ImageDOP Bentic Video Annotations in the Faial-Pico Channel in 2011. 6 records from University of Wyoming Museum of Vertebrates (UWYMV) Herpetology specimens. 248 records from Atlas des Hyménoptères Pompilidae du Massif armoricain et des départements voisins : prospections 2018. 6256 records from FUEL - Herbário da Universidade Estadual de Londrina. 2134 records from Inventario de larvas de peces en la región sur del Golfo de California (GAP 81, 85 y 86) y en el Pacífico Tropical Mexicano (GAP 88-91). 817 records from Midden-Limburg Fish Ponds Survey. 3 records from A new species of Flavoperla Chu, 1929 (Plecoptera: Perlidae) from Guangxi Zhuang Autonomous Region of southern China. 4 records from A remarkable new species of Micropeza Meigen (Diptera: Micropezidae) from Caatinga biome, Brazil. 2743 records from marine sediment metagenome Raw sequence reads. 2 records from The cicada genus Procollina Metcalf, 1952 (Hemiptera: Cicadidae): redescription including fourteen new species, with a key to the species of the subtribe Dazina Kato, 1932 rev. stat., the description of the Aragualnini n. tribe, and one new combination. 31701 records from Herbarium Senckenbergianum (FR) - Fungi. 1 records from A new species of Pristomerus Curtis, 1836 (Hymenoptera, Ichneumonidae Cremastinae) and key to the known species in Iran. 16333 records from Seabirds in Norway - Estimated population sizes. 81 records from Mamíferos de los bosques montanos del Oriente Antioqueño, Cañón del río Melcocho, en el municipio de El Carmen de Viboral, Antioquia - Proyecto Colombia BIO. 1 records from Review of the Eulimnadia (Branchiopoda: Spinicaudata: Limnadiidae) from Argentina with the description of a new species. 247 records from Abundance of large foraminifera in cores from transect NOG-01B, IODP Expedition 325. 12 records from Kenai National Wildlife Refuge, Alaska (KNWR) Fish observations (Arctos). 519 records from Geometridae de France métropolitaine. 843 records from Photographs of higher plants, mosses, fungi, lichens, and algae. 238 records from Vegetación asociada a la ciénaga de Bete, municipio del Medio Atrato, Chocó 2008. 1211 records from Tejidos de ejemplares colectados en el Páramo de Chingaza - Proyecto Colombia Bio. 12 records from Revision of the Palaearctic Trachusa interrupta species complex (Apoidea: Anthidiini) with description of four new species. 2260 records from Leicestershire and Rutland Aculeate Records. 2 records from Two new species of Spider Wasps (Hymenoptera, Pompilidae), Ctenagenia pagliano from Lebanon and Evagetes liane from Canary Islands. 7 records from First record of the genus Agnara (Isopoda: Oniscidea) from Iran with descriptions of two new species. 2144 records from SPC CoFish Invertebrates Observations Marshall Islands 2007. 445 records from South Lanarkshire peatland records 2013. 1 records from Leiolima iberica, a new harvestman genus and species from the Iberian Peninsula (Arachnida, Opiliones, Sclerosomatidae). 8 records from A new genus and five new species of Anostostomatidae from the Lesser Antilles (Orthoptera: Ensifera). 16618 records from Suivi Temporel des Libellules (STELI). 83 records from Données du/de la naturaliste GAUTHIER Nicolas provenant de la base de donnée du SINP Île-de-France CETTIA. 259 records from Derbyshire Casual LEPIDOPTERA records - Casual records collated by Derby Museum.. 682 records from Transferts SI Faune - Données naturalistes opportunistes de Cedric DEVILLEGER. 11 records from The InBIO Barcoding Initiative Database: Portuguese Stag beetles (Coleoptera, Lucanidae). 1 records from A new, peculiar genus of Cossoninae (Coleoptera, Curculionidae) from Oman with description of a new species, larva and notes on biology. 1 records from Revision of the Oriental subgenus Patrisaspilota Fischer, 1995 (Hymenoptera: Braconidae: Alysiinae: Orthostigma Ratzeburg, 1844) with description of a new species from Papua New Guinea. 656 records from RV Investigator Voyage IN2017_V02 Seabird Observations, Australia (2017). 21 records from New distributional records of Staphylinina in Taiwan, including a new species of Miobdelus Sharp (Coleoptera: Staphylinidae: Staphylininae: Staphylinini). 158 records from Birds of Rottnest Island, Western Australia, 1981 - 2007. 329 records from Colección de Alismatales, Apiales, Aquifoliales, Arecales y Asparagales del Museo Botánico CORD - IMBIV. 1 records from Different continents, same species? Resolving the taxonomy of some Holarctic Ancylis Hübner (Lepidoptera: Tortricidae). 1322 records from Herbier National de Guinée (HNG). 1 records from The species of Ctenopelma Holmgren (Hymenoptera, Ichneumonidae) from China. 2 records from A new species of the genus Diogenes Dana, 1851 (Crustacea: Decapoda: Anomura: Diogenidae) from Gujarat, northwestern India. 5 records from New records of Stenopygium Becker (Diptera: Dolichopodidae) from the Neotropical Region, and a key to species. 379 records from Expédition Karubenthos 2012 : inventaire des Echinodermes de la Guadeloupe. 839 records from Iowa State University Fishes Collection. 827 records from Population research on small rodents (Rodentia) and screws (Soridae) in Steinkjer Municipality – Norway; 2018 - 2019 based on systematic catches with ordinary mouse traps in traplines. 455 records from EDIT - ATBI in Gemer area (Slovakia). 8939 records from Global compendium of Aedes albopictus occurrence. 325 records from Inventaire malacologique de la RNR des Marais de Stors. 595 records from Colección de Herpetología de la Universidad del Quindío (HERPETOS-UQ). 88 records from Teich Berlin Wuhlheide. 2 records from Taxonomy of the Cixiidae (Hemiptera, Fulgoromorpha) from the Madeira archipelago. 39 records from On a collection of hydroids (Cnidaria, Hydrozoa) from the southwest coast of Florida, USA. 112 records from Creag Riabhach Wind Farm: 2012-13 Ornithology and Protected Mammal Surveys. 5 records from A new Epeorus (Caucasiron) (Ephemeroptera: Heptageniidae) species from Turkey based on molecular and morphological evidence. 275338 records from Flora Atlas N.T.. 5216 records from E1 Targeted Locus (Loci). 1 records from Klosterlandschaft Maulbronn 19. und 20. Juni 2010. 1435 records from WOLL AVH data. 3 records from A new species of velvet skate, Notoraja sereti n. sp. (Rajiformes: Arhynchobatidae) from Papua New Guinea. 203 records from Insectos de la expedición al municipio de San Francisco, Cundinamarca - Caracterizaciones Humboldt. 1 records from A new species of Dohrnemesa from Brazil, with notes on the male of D. carvalhoi and on D. albuquerquei (Hemiptera: Heteroptera: Reduviidae: Emesinae). 1 records from Two new species in the genus Andronymus Holland, 1896 (Lepidoptera, Hesperiidae). 13 records from New species and new records of Mydidae from the Afrotropical and Oriental regions (Insecta, Diptera, Asiloidea). 373 records from New Mexico Museum of Natural History and Science (NMMNH&S) Herbarium specimens (Arctos). 1 records from Two new species of Hetereleotris (Perciformes: Gobiidae) from the Red Sea. 829 records from Données de la structure SNPN - Société Nationale de Protection de la nature provenant de la base de donnée du SINP Île-de-France CETTIA. 1502 records from Données de la Réserve Naturelle Nationale de Saint-Quentin-en-Yvelines provenant de la base de donnée du SINP Île-de-France CETTIA. 10366 records from Colección de Peces del Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-P). 129 records from Données du/de la naturaliste jourdan christian provenant de la base de donnée du SINP Île-de-France CETTIA. 1 records from New species of Ochodaeus Dejean from Madagascar II (Coleoptera: Scarabaeoidea: Ochodaeidae). 81 records from Revision of the spider genus Hoplopholcus Kulczyński (Araneae, Pholcidae). 92 records from Caddisflies (Insecta: Trichoptera) from Maranhão State, Northeast Region, Brazil: A new species, checklist, and new geographical records. 496 records from Colección de Referencia de Macroinvertebrados Bentónicos del Museo de Ciencias de la Universidad El Bosque. 787 records from HUEMG herbarium - Universidade do Estado de Minas Gerais - Campus Carangola - Herbário Virtual REFLORA. 797 records from Colección base (BGVPA) del Banco de germoplasma del Jardín Botánico Atlántico de Gijón. 3 records from Two new species of the genus Microlysias (Crustacea, Amphipoda, Tryphosidae) from Korean Waters. 3 records from New species of karst-dwelling Pselaphinae from southwestern China (Coleoptera: Staphylinidae). 89002 records from Butterflies of Ireland. 2 records from Rare plants database extract from Scottish Natural Heritage. 2414 records from Données des collections d'algues du MNHN. 474 records from SP-Algae - Herbário do Estado "Maria Eneyda P. Kaufmann Fidalgo - Coleção de Algas. 333 records from Coléoptères Silphidés du département du Loiret. 25 records from A synopsis of Phyllogomphoides Belle, 1970 (Odonata: Gomphidae) of Mexico: taxonomy and distribution. 2 records from Two remarkable new species of oribatid mites (Acari: Oribatida) from Acacia litter of Kerala, India. 9836 records from Formidabel; Belgian Ants Database. 1374 records from Mammifères marins Guadeloupe Antilles françaises (AET). Suppléments. 239 records from Shoreline fish distribution in Italian lakes assessed by electrofishing. 13344 records from University of British Columbia Herbarium (UBC) - Vascular Plant Collection. 1 records from Transfer of two South American ant species from Tapinoma Foerster 1850 to Forelius Emery 1888 (Hymenoptera: Formicidae: Dolichoderinae). 480 records from Isle of Wight non-native invasive species. 2 records from Metrocoris sikkimensis sp. nov. (Hemiptera: Heteroptera: Gerridae) from northeastern India, with a key to species of the compar group occurring in India. 1007 records from Données naturalistes de LUPOLI Roland. 68 records from Données du/de la naturaliste JOSSERAND oriane provenant de la base de donnée du SINP Île-de-France CETTIA. 581 records from Floristic records in the Moscow and Novgorod regions. 154 records from Catopsilia butterfly specimens at Museum Zoologi Bogor, Indonesia. 4 records from A new species of Megatibicen endemic to Mescalero-Monahans shinnery sands (Hemiptera: Auchenorrhyncha: Cicadidae). 1 records from Description of Bagarius vegrandis, a new species of sisorid catfish from Indochina (Actinopterygii: Siluriformes), with notes on the identity of Bagarius bagarius. 535 records from Weber State University Herbarium. 816 records from Inventarios de la biodiversidad en el piedemonte subandino de Yopal. 3 records from Survey of sand flies (Diptera: Psychodidae: Phlebotominae) in Guajará-Mirim State Park forest reserve, near the Brazil-Bolivian border, with a description of Pintomyia fiocruzi, a new sand fly species. 78 records from Données de la naturaliste Anna Even. 96 records from Abundance of macrobenthos organisms in the northern Wadden Sea in 2008. 2 records from Two new species of stargazers of the genus Uranoscopus (Teleostei: Uranoscopidae) from the western Pacific Ocean. 94 records from Molecular phylogeny of the genus Lasiopogon (Diptera: Asilidae) and a taxonomic revision of the bivittatus section. 355 records from Données naturalistes de François BRETON. 816 records from Espèces végetales sur sable roux du fourré de Ranobe, PK 32 Toliara. 5 records from Rare And New For The Fauna Of The Russian Far East Spiders (Aranei). 1 records from A new species of Lepidodactylus (Reptilia: Squamata: Gekkonidae) from the Kei Islands, Maluku, Indonesia. 5 records from Copepoda (Siphonostomatoida: Dirivultidae) from Hydrothermal Vent Fields on the Central Indian Ridge, Indian Ocean. 81 records from Kystfuruskoger i Tysnes og Fusa. 9 records from Nomenclatural changes in the higher classification of the family Tettigometridae (Hemiptera: Fulgoroidea) with description of a new tribe and new species and a review of the Iranian tettigometrid fauna. 362 records from Centre d'Estudis Avançats de Blanes, Macroinvertebrados Limno. 2743 records from EDP Foz Tua: Terrestrial Birds, Winter (point counts) - Ecological Monitoring Program [2011-2017]. 659 records from Modelación de la distribución geográfica de las Orchidaceae del Soconusco. 8 records from Die Bachspezies 2008/2009. 31 records from Big and beautiful: the Megaxyela species (Hymenoptera, Xyelidae) of East Asia and North America. 168 records from Leicestershire and Rutland Reptile Records to 2011. 41018 records from Système d’Information Régional sur la Faune et la Flore - FNE Centre-Val de Loire - Données 2016. 2 records from Review of the New World Notomicrus Sharp (Coleoptera, Noteridae) I: Circumscription of species groups and review of the josiahi group with description of a new species from Brazil. 5640 records from Solenosmilia matrix annotations and VME habitat identification in video from voyage IN2018_V06, Australia (2018). 8 records from Streuobstwiese. 29 records from Collection Vermes - ZMB. 2768 records from SIM-Fungal records compiled by Joan Montón. 130 records from BIRDRACE - The famous Grouse feat. The James. 64836 records from Western Australian Museum provider for OZCAM. 7 records from Parasitoides de Cochinilla. 2 records from Colección de mamíferos voladores y no voladores de la Universidad de Nariño. 82 records from Rückkehr der Biber in Rheinland-Pfalz - Biber in der Primmerbach. 247 records from Flora vascular y no vascular: expedición Cuenca Media del río Chicamocha - Proyecto Boyacá BIO UPTC. 203 records from Migratory shorebirds (sandpipers and plovers) in Hokkaido. 1 records from Mumetopia interfeles sp. nov., a new species of Anthomyzidae (Diptera) occurring en masse in an urban grassy habitat in Chile: its taxonomy, phylogeny and biology. 118 records from Observation des insectes sur le territoire de la Métropole Rouen Normandie. 1 records from New erythroneurine leafhopper species from the Australian realm (Hemiptera: Cicadellidae: Typhlocybinae). 31150 records from Effects of Fecal Input, Environmental Conditions, and Environmental Sources on Enterococci Concentrations in an Estuarine Ecosystem. 43 records from New species of Helicopsyche von Siebold 1856 (Trichoptera: Helicopsychidae) from Brazil, including the redescription of Helicopsyche (Feropsyche) planorboides Machado 1957. 475 records from Anfibios y reptiles de la Sierra Montenegro-Las Trincheras y el cerro el Chumil, Morelos. 38 records from A checklist of the Cleridae of Iran with new data (Coleoptera: Cleroidea). 177 records from Tejidos colectados en la caracterización biótica para la conservación de especies amenazadas en el área de influencia del Oleoducto Bicentenario, departamentos de Arauca y Casanare, Colombia. 16 records from Hazel Dormouse in Ireland. 15684 records from CAS Invertebrate Zoology (IZ). 14 records from Ophioderma hendleri sp. nov. (Echinodermata: Ophiuroidea: Ophiodermatidae) and its congeners from the Eastern Pacific. 41 records from Etude d'impact projet d’ouverture de carrière à Vaudoy-en-Brie. 5515 records from water Raw sequence reads. 3 records from New taxa of Tateidae (Caenogastropoda, Truncatelloidea) from springs associated with the Great Artesian Basin and Einasleigh Uplands, Queensland, with the description of two related taxa from eastern coastal drainages. 55 records from Macroinvertebrados bentónicos de playas de arena (Monte Hermoso-Pehuen Có, Buenos Aires, Argentina). 6 records from A checklist of the Ukrainian Xoridinae (Hymenoptera, Ichneumonidae). 954 records from NW Pacific Deep-sea Benthos Biodiversity (Beneficial Project). 3 records from See lilies of the genus Bathycrinus (Echinodermata, Crinoidea: Bathycrinidae) from the North-West Pacific hadal trenches. 6 records from Leafhopper tribe Coelidiini (Hemiptera: Cicadellidae: Coelidiinae) of the Indian subcontinent. 51404 records from Insects, Outer Hebrides. 36 records from Annotated catalog of the type specimens deposited at the fish collection of the “ Universidade Estadual Paulista, Câmpus de São José do Rio Preto ”, São Paulo, Brazil (DZSJRP). 119 records from Suivi des leucorrines sur le site du Marais du Plata. 17902 records from ALCB herbarium - Universidade Federal da Bahia - Herbário Virtual REFLORA. 2378 records from EDP Baixo Sabor: Construction and Reservoir Filling Phases – Vascular Flora and Habitats: species of conservation concern (RELAPE) - [2010-2014]. 568 records from Philippine Mollusk Symbiont - ICBG Collection. 68 records from Сypripedium guttatum Sw. in the Komi republic. 70 records from Données de la collection de Hubert Piguet - Famille des Elateridae. 5188 records from BioGIS - Vascular plants - Israeli Gene Bank. 2418 records from Flora de las sabanas inundables de las cuencas de los ríos Bita, Manacacías y Cravo Sur - SULU II. 515 records from Kenai National Wildlife Refuge, Alaska (KNWR) Bird observations (Arctos). 7 records from Taxonomic revision of Intybia Pascoe, 1886 species (Coleoptera, Malachiidae) of Thailand and Philippines. 29 records from NSW South Coast & ACT plants. 805 records from EDP Baixo Sabor: Birds - Construction and Reservoir Filling Phases - Vilariça Stream (MC1) [2013-2014]. 31 records from Succession of benthic hard-bottom communities abundance at station Errina2012_CS. 31115 records from 16S rDNA amplicon of Bacteria and Archaea Metagenome. 5 records from A new species of cave dwelling Neocarus (Acari: Opilioacaridae) from Bahia state, Brazil, with remarks on taxonomic characters. 2 records from Museo Provincial de Ciencias Naturales “Florentino Ameghino”, Santa Fe, Argentina - Colección Squamata (no Serpentes) (MFA-ZV-Sq). 1 records from Acantorna-a new genus of Hymedesmiidae (Porifera, Demospongiae Poecilosclerida) from the western Aleutian Islands of Alaska with description of Acantorna tahoma n. sp.. 2 records from A new species of rheophilic cyprinid fish (Teleostei: Cyprinidae) from the Brahmaputra Basin, northeast India. 35 records from Ortsrand Zandershagen. 42 records from An der Weida zwischen Talsperre Zeulenroda und Vorsperre Weida. 61 records from artsprosjektet_48-13_monomyx. 1 records from Crickets of the genus Gryllus in the United States (Orthoptera: Gryllidae: Gryllinae). 8290 records from Akita Prefectural Museum, Observation Records of Birds in Akita Prefecture. 396 records from South Dakota State University, The Severin-McDaniel Insect Research Collection. 505 records from National Frog Survey of Ireland 2010/2011. 2 records from Hieracium attenboroughianum (Asteraceae), a new species of hawkweed. 2 records from A new remarkable and Critically Endangered species of Astyanax Baird & Girard (Characiformes: Characidae) from Chapada Diamantina, Bahia, Brazil, with a discussion on durophagy in the Characiformes. 91 records from Colección Ornitológica de la Universidad del Valle. 104 records from Chronicle of Nature - Phenology of Insects of State Nature Reserve Kivach. 155 records from Chronicle of Nature - Phenology of Plants of State Nature Reserve Privolzhskaya Lesostep. 1 records from A new species of Limnonectes (Amphibia: Anura: Dicroglossidae) from Vietnam. 10 records from Discoveries of the genera Baeochila and Idiocysta from Japan, with descriptions of two new species (Hemiptera: Heteroptera: Tingidae). 7 records from Revision of the South American species of Austrothaumalea Tonnoir (Diptera Thaumaleidae). 1 records from Museo Historia Natural UNAH VS (MUVS) Fish Collection. 490 records from Marine Turtles. 427 records from The ‘ red-tailed’ Lasioglossum (Dialictus) (Hymenoptera: Halictidae) of the western Nearctic. 47 records from An Online Database of the Immatures of Coleoptera (Arthopoda, Insecta) Described from Brazil. 188 records from Données de Mammifères marins. Mission Sanctuaire AGOA de 2012 à 2014. 5 records from A new species of Sarmydus Pascoe, 1867 (Cerambycidae: Prioninae: Anacolini) from Nicobar Island, India. 576 records from Waarneming.nl (NL) - Great Grey Shrike Count 2009-2010. 1 records from First record of the genus Chandleriella Hlaváč (Coleoptera: Staphylinidae: Pselaphinae) from China, with description of a second species. 240 records from Evaluación del macrobentos de la plataforma continental del Caribe colombiano. 1 records from Description of a new species of Megischus Brulle (Hymenoptera, Stephanidae), with a key to the species from China. 2962 records from Alterra (NL) - Microarthropods inventory in calcareous grasslands. 161 records from Ten new species of Phyllodoce Lamarck, 1818 (Phyllodocidae, Annelida) from Brazil. 14 records from The Goblin spider genus Xestaspis in Sri Lanka (Araneae: Oonopidae). 154 records from Chronicle of Nature - Phenology of Birds of Central Forest State Nature Biosphere Reserve. 3 records from British Reptiles & Amphibians in the collections of World Museum Liverpool. 5 records from Vermont Orthoptera Records from Historic Dot Maps. 8006 records from Segunda caracterización biológica de aves del proyecto "Incorporación de la Biodiversidad en el sector cafetero en Colombia". 1 records from A new sand frog from Namaqualand, South Africa (Pyxicephalidae: Tomopterna). 14 records from Revision of the genus Nephelomilta Hampson, 1900, with descriptions of twelve new species and two new subspecies (Lepidoptera, Erebidae, Arctiinae). 30558 records from Données de l'Observatoire de la Faune de Bourgogne. 6 records from Review of Scatimus Erichson (Coleoptera: Scarabaeidae) in Colombia with the description of a new species. 2226 records from Colección Herpetológica (Reptiles) del Museo de Historia Natural de la Universidad Industrial de Santander. 1930 records from Fungi of parks, forests and reserves of New Jersey, 2018. 112923 records from Wild bees of Belgium. 114 records from Host associations of Melanterius Erichson (Coleoptera: Curculionidae: Cleogonini), with a diagnosis and delimitation of the genus and description of five new species. 2 records from Taxonomic review of the genus Paranisitra Chopard (Orthoptera: Gryllidae: Eneopterinae: Nisitrini) with description of a new species from Mindanao. 3 records from Review of the genus Pseudolathra Casey, 1905 (Coleoptera: Staphylinidae: Paederinae) of Réunion Island. 22 records from Observations de tortues marines dans l'archipel de Saint-Pierre et Miquelon. 54 records from Données du/de la naturaliste Villalta Rémi provenant de la base de donnée du SINP Île-de-France CETTIA. 89 records from Demosponges from the sublittoral and shallow-circalittoral (<24 m depth) Antarctic Peninsula with a description of four new species and notes on in situ identification characteristics. 5 records from New species of the plesiomorphic genus Nixonia Masner (Hymenoptera, Platygastroidea, Platygastridae) from South Africa. 1207 records from Microbial diversity studies of Arabian Sea sediment. 756 records from Mokihinui and Karamaea small tributaries and seeps. 6466 records from Anillamiento de Aves Sierra Nevada de Santa Marta - Proyecto Cruzando el Caribe. 177 records from Museu de Ciències Naturals de Barcelona: MCNB-Tissue. 242 records from Aspilanta new genus (Heliozelidae) specimen data. 143 records from Echinoderms from the Seaflower Biosphere Reserve. 558 records from If_Ecologie_Conseil_2017_12_18. 646 records from Coleção Zoológica de Referência da Universidade Federal de Mato Grosso do Sul - Hemiptera (ZUFMS-HEM). 24 records from Colección de diatomeas del Herbario "Jaime Andrés Rodríguez". LEB-Diatomea. 4 records from Reassessment of the taxonomic status of Pseudopaludicola parnaiba (Anura, Leptodactylidae, Leiuperinae), with the description of a new cryptic species from the Brazilian Cerrado. 264 records from Rescate de epífitas Oleoducto Bicentenario, Tramo Araguaney - Banadía (rescate). 16263 records from Allan Herbarium (CHR). 368 records from Biological Recording in Scotland - Bumblebee Survey. 9910 records from Field Museum of Natural History (Zoology) Invertebrate Collection. 687 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase (Plantas Tapachula). 1 records from A new species of iguanid lizard, genus Stenocercus (Squamata, Iguania), from the Central Andes in Peru. 140 records from Taxonomic revision of West African cone snails (Gastropoda: Conidae) based upon mitogenomic studies: implications for conservation. 6 records from Redescription of Hypostomus carinatus (Steindachner 1881) (Siluriformes: Loricariidae) from the rio Amazonas basin in Brazil. 15 records from Two new sympatric species of Stenocercus (Squamata: Iguania) from the inter- Andean valley of the Mantaro River, Peru. 421 records from Monitoreo biológico en la cuenca La Paila, campaña ARA - RARE - CVC – Asociación Calidris. 1355 records from Antarctic Lakes Brine Raw sequence reads. 1 records from Lanlabeo duanensis, a new genus and species of labeonin fish (Teleostei: Cyprinidae) from southern China. 24 records from MVZ Herp Observations (Arctos). 5 records from A review of the Neotropical microcaddisfly genus Acostatrichia Mosely, 1939 with description of a new species from Brazil (Trichoptera: Hydroptilidae: Leucotrichiinae). 1 records from A new Portholefish of the genus Diplophos (Stomiiformes: Gonostomatidae) from the western Pacific Ocean. 5938 records from Plan Aménagement et de Gestion Simplifié (PAGS) des forêts galeries des départements de l'Ouémé-Plateau. Data mobilized in the framework of a JRS Biodiversity Foundation project in Benin. 25 records from Inventario de Murciélagos Buenos Aires, Tauramena, Casanare. 20 records from Bulletin de la Société Linnéenne de Bordeaux, Tome 143 (N.S) n° 36 (1), 2008 - Données faune. 55 records from Agromyzidae (Diptera: Schizophora) in the state of Pará: new species and new records in Brazil. 8367 records from Aves Acuáticas de las sabanas inundables del Meta y Casanare. 251 records from Données naturalistes d'Olivier LAURENT. 5892 records from Restauración y conservación de Isla Guadalupe. 56 records from Lepidoptera (Specimens NRM). 4 records from Coleção de Coleoptera da Universidade de Brasília. 208 records from Colección nacional de palmas de Colombia - JBQ. 15327 records from Biodiversidad asociada al gasoducto Paiva-Caracolí. 1290 records from Diversity of Spiders from Azorean Trails. 42 records from Ensemble des données Orthoptères. 13 records from Lane 6 Analysis. 10354 records from Inventaire de la flore de Charente-Maritime 2018. 64 records from Chronicle of Nature - Phenology of Insects of Tigirek State Nature Reserve. 3 records from A new species of Capnia (Plecoptera: Capniidae) from Lesser Khingan Range (Amur River Basin, Far East of Russia). 2 records from A new species of Pelthydrus (s. str.) Orchymont, 1919 from Yunnan, China (Coleoptera: Hydrophilidae: Hydrophilinae: Laccobiini). 5 records from Pauximyia, a new genus of Odiniidae (Diptera: Acalyptratae) with description of two new species from Brazil. 2 records from First record of the leafhopper genus Xenovarta Viraktamath (Hemiptera, Cicadellidae, Deltocephalinae) from India with description of a new species. 18 records from Lepidurus arcticus survey Northeast Greenland 2013. 2808 records from Natura 2000 Vallée de la Seille. 10894 records from Occurrences of the invasive plant species Heracleum sosnowskyi Manden. in the Komi Republic territory (European North-East Russia). 153 records from VSN-Wiese. 19054 records from IMPACT OF SAHARAN DUST DEPOSITION ON BACTERIOPLANKTON IN MARINE SURFACE WATER. 30 records from Additions to the list of Finnish Bibionomorpha (Diptera, Nematocera). 63085 records from Alien plant presence dataset from the point-radius plot surveys in 2010-2015 in Taiwan. 1657 records from Colección de insectos agrícolas del proyecto diversidad en sistemas de cultivos. 2 records from A new species of Liriomyza Mik (Diptera, Agromyzidae) on okra in Brazil. 1612 records from Ibaraki Nature Museum, Fungi collection. 2 records from A new genus and species of anophthalmous Otiorhynchini from Greece, with a new synonymy and new combinations (Coleoptera: Curculionidae, Entiminae). 1785 records from 3Soil16S. 791 records from EDP Baixo Sabor: Construction and Reservoir Filling Phases: Cliff-nesting Birds, priority conservation species: Complementary Observations - [2010-2014]. 29 records from Fortalecimiento de la efectividad del manejo y la resiliencia de las áreas naturales protegidas para proteger la biodiversidad amenazada por el cambio climático. 1984 records from Colección de Reptiles - Museo de Herpetología de la Universidad de Antioquia. 67 records from Relative abundance of ostracods in sediment core Sv09. 896 records from Chironomid Specimen records in the Chironomid DNA Barcode Database.. 3 records from Révision du genre Danuriella Westwood, 1889 (Mantodea). 31189 records from Amis_des_Marais_du_Vigueirat_2017_12_18. 3 records from New species and records of the Neoserica (sensu stricto) group (Coleoptera: Scarabaeidae: Sericini). 3 records from Holomorphology and Neotype designation of Microperla geei Chu, with egg morphology of Microperla qinlinga Chen (Plecoptera: Peltoperlidae). 49 records from Atelier Malacologie continentale, 14-15septembre, La Flèche (Sarthe). CEN Pays de la Loire. 454 records from Catalogue and description of the coccolithophores (Haptophyta, Coccolithophyceae), calcareous, scale-bearing microalgae, in New Zealand waters. 23136 records from PAH-contaminated sediment from the Lagos Lagoon, Nigeria. 10 records from New species of Hercostomus Loew, 1857 from Afrotropics (Diptera: Dolichopodidae) and key to Afrotropical fauna. 22368 records from R. L. McGregor Herbarium Lichen Collection. 660 records from Peces pelágicos de la Isla Cayo Serrana durante la Expedición Seaflower 2016 - Proyecto Colombia BIO. 1 records from A revision of the spider genus Anemesia (Araneae, Cyrtaucheniidae). 47 records from Distribución de la Nutria (Lontra longicaudis) en la cuenca baja del río Sinú en el departamento de Córdoba. 11033 records from Oregon Bee Atlas Survey Data: 2018. 1 records from Description of a new species of the genus Cnemaspis Strauch, 1887 (Reptilia: Squamata: Gekkonidae) from the Nilgala Savannah forest, Uva Province of Sri Lanka. 7 records from Birds Specimens of Akita Prefectural Museum. 74 records from Coleção de Bryozoa do Museu Nacional - UFRJ. 2315 records from UAM Fish Collection (Arctos). 2 records from A new micropterous species of Leuctra (Plecoptera: Leuctridae) from the Lesser Caucasus (Georgia). 5 records from University of Sargodha Herbarium. 8808 records from Survey of bumblebees in central Alberta - 2018. 1 records from A new species in the troglomorphic scorpion genus Troglotayosicus from Colombia, representing the northernmost known record for the genus (Scorpiones, Troglotayosicidae). 2 records from A new species of Phlogophora Treitschke (Lepidoptera: Noctuidae) from China. 70 records from Isotope tracer experiment: meiofauna counts. 100 records from Données naturalistes de LE GLOANEC Vincent. 14 records from Bird Specimens of The Cattle Museum. 743 records from Coleção Zoológica de Referência da Universidade Federal de Mato Grosso do Sul - Reptilia (ZUFMS-REP). 4 records from New data on the Pterophoridae fauna of Liberia (Lepidoptera: Pterophoridae). 2 records from A new species of the genus Microhyla Tschudi, 1838 (Amphibia: Anura: Microhylidae) from Tay Nguyen Plateau, Central Vietnam. 1847 records from ERBG AVH data. 49793 records from CABI Africa Invasive and Alien Species data. 20132 records from River Biologists' Database (EPA). 11017 records from Banded Iron Formation and Greenstone survey data. 230 records from Biometría peces Parque Nacional Natural La Paya. 55 records from Great Eastern Ranges - Slopes to Summit. 1366 records from UCM Mammal Collection (Arctos). 41 records from Hydroptilidae (Trichoptera) of Angola, a new genus, seven new species, and five new records. 2 records from New records and checklist of Chilocorini (Coleoptera: Coccinellidae) from China. 5699 records from Tiroler Landesmuseum Ferdinandeum. 4 records from The bees of the genus Colletes Latreille (Hymenoptera: Colletidae) of the Caucasus region. 91 records from Anfibios y reptiles de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 13868 records from Données faune Nature 18 - 2017. 43596 records from Natural History Museum, Vienna - Herbarium W. 104 records from BIRDRACE Die Vriesischen Feigen-Vögel (VFV). 3298 records from Odonata records from RSPB Reserves 1970-2009. 1 records from Siccia imana, a new species from Rwanda (Lepidoptera: Erebidae: Arctiinae). 9 records from A new species of Proterhinus Sharp, 1878 (Coleoptera: Curculionoidea: Belidae) from Miti‘aro, Cook Islands, South Pacific. 849 records from Données supplémentaires Atlas des Mammifères marins. 53 records from Données du/de la naturaliste Dubois Yves provenant de la base de donnée du SINP Île-de-France CETTIA. 986 records from University of Colorado, Museum of Natural History Herbarium Bryophyte Collection. 866 records from DREAL_PACA_-_N2000_-_Parc_Naturel_Régional_du_Verdon_2017_12_18. 65 records from Biologia reprodutiva e dieta de Amerotyphlops brongersmianus (Vanzolini, 1976) da Restinga de Jurubatiba, Rio de Janeiro, Brasil (Serpentes: Typhlopidae). 30 records from Feral Pigs - Sightings and Cull records - 2014-2015. 7 records from Leptobasis linda sp. nov. from Ecuador (Odonata: Coenagrionidae). 1 records from On the systematic status of Calliophis macclellandi nigriventer Wall, 1908 (Reptilia: Serpentes: Elapidae). 18 records from Anfibios presentes en el Cerro Jánano. 2 records from Two new species of the genus Malayepipona Giordani Soika (Hymenoptera: Vespidae: Eumeninae) from Vietnam, with updated key to all recognised species. 120 records from Données espèces - Expertise IPE 79. 22 records from Mesostigmatic mites (Acari: Mesostigmata) of Saudi Arabia (excluding Phytoseioidea), new records and a key to the known species. 711219 records from NBIS Records to December 2016. 1 records from Description of the larva of Orthemis ferruginea (Fabricius, 1775) (Odonata: Libellulidae). 305 records from Rohrmeistereiplateau und angrenzendes Gebiet. 1748 records from Floral visits on plants, InsectScale 2008. 1 records from Thraulodes marianoi sp. nov., a remarkable new species of mayfly (Ephemeroptera Leptophlebiidae) with dark wings from the southern Brazilian Atlantic Forest. 935 records from Survey and monitoring records for Scottish Wildlife Trust reserves from reserve convenors and Trust volunteers - Unassessed data. 2509 records from Kenya Wildlife Service, Laikipia Samburu Aerial Census, 2012. 1 records from New record for the deep-sea genus Tripoplax (Mollusca: Polyplacophora) in the eastern Pacific. 45 records from South American Antarctic Marine Biodiversity Literature. 25456 records from Arizona State University Vascular Plant Herbarium. 1 records from Tibetyrus gen. nov., a new myrmecophilous Tyrini from Xizang, China (Coleoptera: Staphylinidae: Pselaphinae). 81 records from Métropole_Nice_Côte_d'Azur_2017_12_18. 39 records from Stoneworts in Wales. 19 records from City of Edinburgh Natural Heritage Service - Large Red Damselfly Survey. 3 records from Two new species of tribe Agalliini (Hemiptera: Cicadellidae: Megophthalminae) with note on intraspecific variations. 308 records from Naturmiljø Bergensbanen 2015 (project number 616033). 87 records from Données espèces - Expertise IPE 70. 940 records from NOAA coral reef monitoring invertebrate data from sites across Micronesia from 2009-09-29 to 2015-09-25. 12 records from Two new genera and three new subterranean species of Hydrobiidae (Caenogastropoda: Truncatelloidea) from Tunisia. 1930 records from Données de la naturaliste Lemoine Delphine provenant de la base de donnée du SINP Île-de-France CETTIA. 17 records from Thirteen new records of ferns from Brazil. 99 records from Modelación de la distribución y abundancia de las subespecies de venado cola blanca en México: implicaciones de conservación y manejo. 3 records from Delimitation and description of three new species of Himalopsyche (Trichoptera: Rhyacophilidae) from the Hengduan Mountains, China. 3 records from A new species of the flower bug genus Orius Wolff (Hemiptera: Anthocoridae) cryptically inhabiting Hibiscus tiliaceus L. (Malvaceae). 1 records from A review of the genus Beltia Jacoby (Chrysomelidae: Eumolpinae: Eumolpini), with descriptions of fourteen new species from Costa Rica, Panama, and northwestern South America. 8 records from The InBIO Barcoding Initiative Database: A taxonomic revision of the Western Palaearctic genus Cacochroa Heinemann, 1870 (Lepidoptera, Depressariidae). 192 records from Steinbruch Mainz-Weisenau, 2. Jahr. 669 records from LSU Shirley C. Tucker Herbarium at Louisiana State University - Lichens. 2302 records from NE Scotland other invertebrate records 1800-2010. 10175 records from NE AVH data. 98 records from Description of lithologic section units of IODP Hole 325-M0033A. 109 records from Birdrace-Di_Bi_Di_Birder-Wesel. 21 records from New species and records of Leuctridae (Plecoptera) from Guangxi, China, on the basis of morphological and molecular data, with emphasis on Rhopalopsole. 25 records from Base de données en ligne d'observations naturalistes de mammifères marins. GEPOG & LPO. 16 records from Caddisflies (Insecta: Trichoptera) from Santa Catarina Lachatao, Oaxaca, México: New species, new geographical records, and checklist. 1820 records from Biodiversidad selecta de los humedales de Laguna de Términos - Pantanos de Centla (Plantas). 99 records from Schwanner Warte / Kinderhaus St. Elisabeth Waldplatz. 98 records from Données opportunistes sur les odonates. 170 records from Earthworm Research Group (UCLan) Earthworm Records (UK). 5 records from Myrmeleon almohadarum sp. nov., from Spain and North Africa, with description of the larva (Neuroptera Myrmeleontidae). 5887 records from Données Entomologiques A. HORELLOU 1988-2018. 2 records from A new species of Paralithoxus (Siluriformes: Loricariidae: Ancistrini) from the highlands of Serra da Mocidade, Roraima State, Brazilian Amazon. 82 records from University of Jena, Herbarium Haussknecht - Herbarium JE. 2 records from A new species of Polyamia DeLong (Hemiptera: Cicadellidae: Deltocephalinae: Deltocephalini) representing the first record of the genus from South America. 285 records from Données du/de la naturaliste Cousin Richard provenant de la base de donnée du SINP Île-de-France CETTIA. 5619 records from The rhizosphere microbiome of burned holm-oak: potential role of the genus Arthrobacter in the recovery of burned soils. 632 records from 2019_NSMK_PL. 3093 records from Establecimiento de un área protegida en el Alto y Bajo Calima, área clave de biodiversidad en el Valle del Cauca, Colombia. 12350 records from Enquête Lucane. 18 records from ZUEC-ECH - Coleção de Echinoidea do Museu de Zoologia da UNICAMP. 1275 records from Records of Halicarcinus planatus at sub-Antarctic regions. 716 records from Observations de Coléoptères saproxyliques de Frédéric LACOSTE. 4 records from The cicadas (Hemiptera: Cicadidae) of Ecuador including the description of five new species, a new subtribe, four new synonymies, and fifteen new records. 22 records from Site Condition Monitoring of dragonflies on Loch aí Mhuilinn SSSI potential extension - 2016. 2 records from The first record of the family Chloroperlidae (Plecoptera) from the Guangxi Zhuang Autonomous Region of southern China, with description of a new species of Sweltsa Ricker, 1943. 205 records from Wild boar sightings held by Andy Riches. 78 records from Chronicle of Nature - Phenology of Birds of FSBI United Administration of the Lazovsky State Reserve and National Park Zov Tigra. 87 records from Chronicle of Nature - Phenology of Insects of Baikalsky State Nature Biosphere Reserve. 6 records from Wuhle - Brücke / B1. 3 records from A new western Atlantic snapping shrimp of the Alpheus macrocheles group (Caridea, Alpheidae) revealed by morphological, molecular and color data. 2192 records from Marie-Victorin Herbarium (MT) - Bryophytes. 2 records from New enigmatic species of the genus Pediobius (Hymenoptera, Eulophidae) from Afrotropics, with notes on related genera. 489 records from Caracterización bionómica de zonas de dragado y de afección de obras en la Ría de Ferrol. 2 records from Código de barras de ejemplares de la Colección Nacional de Mamíferos del Instituto de Biología, UNAM. 52 records from First records and two new species of sipunculans (Sipuncula) from the Southern Mexican Pacific. 2570 records from Collection of saproxylic and xylobiont Beetles. 2747 records from Compost microbe establishment and growth in agricultural soils. 781 records from Composición florística y estructura de tres parcelas permanentes en diferentes estados sucesionales en transición de bosques húmedos tropicales con bosques secos tropicales del municipio de Lebrija, Santander (Primer censo). 29619 records from National Benthic Inventory. 2 records from Two new species of Helicopsyche Siebold 1856 (Insecta: Trichoptera: Helicopsychidae) from Pará State, northern Brazil. 9988986 records from The Danish Environmental Portal, species and habitats-database "Danmarks Miljøportals Naturdatabase". 19 records from EDP Foz-Tua: Nocturnal Birds - Complementary Studies [2010]. 415 records from Caracterización de vegetación para el establecimiento de límites funcionales de humedales: Ciénaga de la Virgen, Ciénaga Zapatosa y Complejo Hato Corozal - Paz de Ariporo. 358 records from Comunidad fitoplanctónica presente en la Bahía de Buenaventura 2018. 111 records from BIRDRACE Die Wendehälse. 9599 records from Tachinid Recording Scheme - GB and Ireland records. 3 records from Review of genus Hydropsyche Pictet 1834 (Insecta: Trichoptera: Hydropsychidae) from India. 5 records from Thoridae (Crustacea: Decapoda) can penetrate the Abyss: a new species of Lebbeus from the Sea of Okhotsk, representing the deepest record of the family. 3 records from Denitrification bacteria in sediment cores of Daya Bay, China. 6 records from Five new species of Nazeris Fauvel in Guangxi, China (Coleoptera, Staphylinidae, Paederinae). 5 records from Données naturalistes de Mikaël PAILLET. 4379 records from Wild Bee Specimens from Blueberry and Raspberry Farms in the Champlain Valley, Vermont, USA. 3301 records from Données de type contact en Guadeloupe. 266 records from Utah State University, Intermountain Herbarium. 2 records from First records of the jewel beetles Chrysobothris desmaresti (Laporte & Gory, 1836) and Hiperantha stempelmanni Berg, 1889 (Coleoptera: Buprestidae) in Bolivia. 1078 records from Finnish Floristic Database (Vascular plant data of Kevo Subarctic Research Institute). 119 records from HUCP herbarium - Pontífica Universidade Católica do Paraná PUC - Herbário Virtual Reflora. 327 records from The Sphecid Wasps of the genus Cerceris L, 1802 of the " Biologiezentrum Linz " - Collection in Linz, Austria, from the Palearctic Region (part II). (Hymenoptera, Apoidea, Crabronidae). 3195 records from Flora presente en 7 parcelas permanentes ubicadas en el Valle del Cauca. 657 records from Herpetofauna de la región del Mar Muerto, Oaxaca-Chiapas. 5772 records from A grid-based database on vascular plant distribution in Samoylovsky District of Saratov Oblast, Russia. 5 records from IRKU Herbarium: collections of vascular plants. 42 records from "Natur macht Schule 2" Natur im Wohngebiet Gorndorf. 6 records from New and little known species of Eumolpinae (Coleoptera: Chrysomelidae) from Northern Vietnam. 3 records from A new, uniquely patterned spiny eel (Teleostei: Mastacembelidae) from southern Borneo, Kalimantan Tengah, Indonesia. 55 records from Galls on Beech Trees in Hainich, 2008. 15 records from Three new species of Holoscolex (Clitellata, Glossoscolecidae) from the Gurupi Biological Reserve, last forest remnant of the Belém Endemism Area, Eastern Amazon. 6 records from New species of Anaptomecus Simon, 1903 (Araneae: Sparassidae) from Colombia, with an identification key for all known species of the genus. 1596 records from Microbial communities in deep eastern Mediterranean Sea surface sediments. 1506 records from Atlas des Poissons et Crustacés d'eau douce de Guadeloupe. 14957 records from CAS Entomology (ENT). 4019 records from Inventario multitaxonómico del ANP Médanos de Samalayuca. 132921 records from Carnet B Lorraine. 1 records from Naturalis Biodiversity Center (NL) - Pisces. 31 records from Ecosystems of the sandstone region incl. sand-belt (SE of Melb.). 8 records from A new species of Cetopsis from the Guiana Shield (Siluriformes: Cetopsidae: Cetopsinae). 3 records from Eine neue Art der Gattung Quedius STEPHENS aus Syrien (Coleoptera, Staphylinidae, Staphylininae, Staphylinini, Quediina. 126 records from Myxomycetes collection of the University of Eastern Finland. 61595 records from Données du/de la naturaliste Bottinelli Julien provenant de la base de donnée du SINP Île-de-France CETTIA. 312005 records from Seasearch Marine Surveys in England. 20 records from New data on the fauna of China, part I: the taxonomy of the millipede family Julidae (Diplopoda). 15 records from The water mite genus Aspidiobates Lundblad, 1941 from Australia (Acari: Hydrachnidia: Hygrobatidae) with the description of two new species. 122 records from Comunidad íctica del atolón Albuquerque durante la Expedición Seaflower 2018 - Proyecto Colombia BIO. 7 records from A review of the genus Coccoglypta Pilsbry, 1895 (Gastropoda: Pulmonata: Camaenidae). 1 records from Données de Mammifères marins dans les TAAF et autres territoires issues de la bibliographies. Compte cardobs 1007 (Trudelle). 308 records from Tejidos de la expedición en el páramo de Rabanal, Boyacá - Proyecto Boyacá BIO. 72 records from Chronicle of Nature - Phenology of Insects of Pechoro-Ilych State Nature Reserve. 53 records from Données malacologiques continentales de Julien Ryelandt (CORSE 2017). 1 records from Macrochelid mites (Mesostigmata: Macrochelidae) from São Paulo state, Brazil, with description of a new species of Macrocheles. 11 records from Seven new species of the Stenus cirrus group (Coleoptera, Staphylinidae) from Guangxi, South China. 17 records from The genus Leucophenga (Diptera, Drosophilidae), part VII: the subpollinosa species group from China, with morphological and molecular evidence. 170 records from SNH Invertebrate Site Condition Monitoring 2013/14: Eastern Cairngorms SSSI. 9634639 records from Pl@ntNet automatically identified occurrences. 2 records from Description of lithologic section units of IODP Hole 325-M0052C. 1 records from Molecular phylogeny reveals strong biogeographic signal and two new species in a Cape Biodiversity Hotspot endemic mini-radiation, the pygmy geckos (Gekkonidae: Goggia). 97 records from Amphibiens filet/Marbotte-Ronval 2013. 3 records from Black Corals (Anthozoa: Antipatharia) from the Southwestern Atlantic. 5176 records from Amphibiens et Reptiles de France (Enquête 2). 1 records from A new species of glass sponge (Hexactinellida: Sceptrulophora: Uncinateridae) from the Weijia Seamount in the northwestern Pacific Ocean. 2126 records from Dolichopodidae of Portugal - dataset 2009-2018. 3136 records from Inventario de la biota marina (cnidarios, poliquetos, moluscos, crustáceos, equinodermos y peces) del Santuario Islas e Islotes de Bahía Chamela, Jalisco, México. 7178 records from Ravensthorpe Range survey data. 140 records from SNH Invertebrate Site Condition Monitoring 2015: Blind Moss SSSI. 2063 records from artsprosjektet_48-15_naididae. 2741 records from Données naturalistes d'Alain BERLY. 1401 records from Insect Collection from the Museu Nacional de História Natural e da Ciência, Universidade de Lisboa, Portugal. 9 records from Two New Liocranid Species Records From Turkey (Araneae: Liocranidae). 625 records from Données opportunistes. 21 records from City of Edinburgh Natural Heritage Service - Harperrig Otter Survey. 2413 records from Auburn University Museum of Natural History Mollusks. 7191 records from Yoann_BLANCHON_2017_12_18. 201 records from Inventaire et regroupement de données Natura 2000. 11424 records from Données bibliographiques et opportunistes Mammifères du Nord Pas-de-Calais issues du SIRF. 121164 records from Données de la flore d’Alsace (SBA). 77 records from Suivi naturaliste du Parc du Peuple de l'Herbe. 1756 records from Moluscos de la Colección de Referencia de Biología Marina de la Universidad del Valle (CRM-UV). 56 records from Données du/de la naturaliste Goncalves Cristina provenant de la base de donnée du SINP Île-de-France CETTIA. 22 records from Typotheca of the higher vascular plants stored in M.G. Popov Herbarium (NSK) at the Central Siberian botanical garden SB RAS. 2126593 records from RSPB Big Garden Birdwatch winter sightings in the UK in 2009. 10 records from Données naturalistes de Sophie COHEN. 696 records from the diversity of anammox bacteria in the subterranean estuary. 21758 records from Données Mammifères Midi-Pyrénées enregistrées dans BazNat - Lot 1. 1 records from The spider wasp genus Telostholus Haupt, 1929 (Hymenoptera, Pompilidae) in Malaysia, with the description of four new species. 3488 records from Wikiplantbase #Sicilia. 129 records from NEON Biorepository Zooplankton Collection (Unsorted Bulk Sample). 1451 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México, segunda etapa 2008-2009 (Región golfo centro). 142 records from Paguroids (Decapoda: Anomura: Diogenidae and Paguridae) of the remote oceanic Archipelago Trindade and Martin Vaz, off southeast Brazil, with new records, description of three new species and zoogeographical notes. 2 records from Two new species of Rhopalopsole (Plecoptera: Leuctridae) from China. 11 records from Review of the aquatic Hemiptera from Cephalonia, with a checklist for the Ionian Islands, Greece (Heteroptera: Gerromorpha, Nepomorpha, Leptopodomorpha). 214 records from Naturpark Kottenforst-Ville Sammelaktion 15.-19.6.. 498 records from Bekkelag basin, Inner Oslofjord. 4 records from Description of a new species of Enispa Walker, 1866 (Lepidoptera: Erebidae, Boletobiinae) from Thailand. 2023 records from Composición florística y estructura vegetal de una parcela permanente en un relicto de bosque seco tropical en el Caribe colombiano. 292 records from Regroupement de données Oiseaux d'eau. 108 records from Phenological Center - Birds (Laplandskiy). 1 records from Cabdio crassus, a new species of cyprinid fish (Teleostei: Cyprinidae) from the Kaladan River of Mizoram, India. 1925 records from Caracterización de la vegetación en una zona delimitada en Cumbitara, La Llanada, Policarpa y Los Andes Sotomayor (Nariño), como insumo para la identificación de oportunidades de conservación para la recuperación de los servicios ecosistémicos de bosque seco. 57 records from Inventaire faune flore de l'étang d'Abbecourt à Orgeval. 14387 records from Grasshopper and Cricket (Orthoptera) and related species records from Britain and Ireland to 2007. 1 records from dust metagenome Raw sequence reads. 1 records from Two new sponge-associated Branchiosyllis (Annelida: Syllidae: Syllinae) from Northeastern Brazil. 11 records from SNH Invertebrate Site Condition Monitoring of Beetle Assemblage Features 2015: Glen Tarff SSSI. 3 records from A new species of long-legged terrestrial Terrapotamon Ng, 1986 (Crustacea: Brachyura: Potamidae) from limestone formations in Satun, southern Thailand. 76 records from BIRDRACE Nachtigallen. 1284 records from ConDidact Citizen Science Surveys - Amphibians 2007. 61 records from Données de Midi-Pyrénées transmises par Pascal Peyrache.. 13 records from Données naturalistes de THÉVENOT Jessica. 250 records from Deep Sea fishes (Chondrichthyes, Osteichthyes) in the Southwestern Colombian Caribbean. 35074 records from Inventaire de la flore de Lot-et-Garonne 2017. 1 records from Données du/de la naturaliste LUSTRAT Philippe provenant de la base de donnée du SINP Île-de-France CETTIA. 129 records from SNH Invertebrate Site Condition Monitoring 2013/14: Glenmore Forest SSSI. 6 records from Swedish Malaise Trap Project (SMTP) - Banchini. 56 records from Taxonomy and molecular phylogeny of the Platystictidae of Sri Lanka (Insecta: Odonata). 1 records from First description of the male of the eyeless spider Draconarius tortus Chen, Zhu & Kim 2008 from China (Araneae: Agelenidae: Coelotinae). 1 records from Revision of the Neotropical genus Macreupelmus Ashmead (Hymenoptera: Chalcidoidea: Eupelmidae). 3 records from Indian Hecalina (Hemiptera: Cicadellidae: Deltocephalinae: Hecalini) with description of three new species. 2 records from Revision of the Australian Wet Tropics endemic rainbowfish genus Cairnsichthys (Atheriniformes: Melanotaeniidae), with description of a new species. 1 records from Dorcus tianlongi, a new species from central China (Coleoptera: Lucanidae: Lucaninae). 1175 records from Colección de Geraniales hasta Lamiales del Museo Botánico CORD - IMBIV. 206 records from Surveys of the East Coast Akalat, Sheppardia gunningi, in Arabuko-Sokoke Forest, 2005-2011. 333 records from Données naturalistes de Renaud PUISSAUVE. 64253 records from Dry Tortugas Reef Visual Census 2010. 237 records from Suivi ornithologique par IPA et IKA réalisés dans la Réserve nationale de l’Étang de Saint-Paul en 2012 et 2014. 2 records from Dolichogenidea fernandeztrianai sp. nov. (Hymenoptera: Braconidae, Microgastrinae) from Iran. 3 records from Universidad de Murcia, Dpto. Biología Vegetal (Botánica), Murcia: MUB-HEPATICAE. 1 records from Nomenclatural changes in Mymaridae (Hymenoptera: Chalcidoidea). 5 records from New species of Culex (Culiciomyia) (Diptera: Culicidae) from Talangaye Forest in Cameroon and descriptions and identification keys for males of the Afrotropical species of the subgenus. 1 records from Marine algal (seaweed) flora of Faial Island, Azores. 1 records from Contribution to the Asian and Afrotropical species of the genus Dyschiriodes (Coleoptera: Carabidae: Scaritinae). 1 records from Discovery of the Dinoponera lucida male (Hymenoptera, Formicidae), a threatened giant ant from the Atlantic rain forest. 6 records from Revision of the bee genus Bathanthidium Mavromoustakis (Hymenoptera: Apoidea Megachilidae: Anthidiini) with description of a new species from China. 5 records from A new pelvic-less species of Melanorivulus Costa (Cyprinodontiformes: Cynolebiidae), with a discussion on the pelvic-fin absence in killifishes. 107 records from Three new species of Oxypoda from Spain, Armenia, and Ukraine with notes on the fauna of Armenia (Coleoptera: Staphylinidae: Aleocharinae). 1 records from The Calliphoridae (Diptera) of Armenia. 651 records from Réseaux écologiques/Trame verte et bleue. 21 records from New data on brachypterous Paederus (Coleoptera, Staphylinidae) of mainland China. 89 records from données araneologiques de LEENKNEGT Virginie. 3500 records from Pelagic sediment metagenome of Gulf of Kutch. 3 records from A new species of Neoperla (Plecoptera: Perlidae) from southeastern Tibet of China with additions to the knowledge of N. perspicillata Zwick, 1980. 4 records from Herbarium Senckenbergianum (FR) - Protista. 875 records from Herbario virtual bosques secos de Colombia - Sección herbario ICESI. 6393 records from VegetWeb - Repositorium von Vegetationsaufnahmen. 82 records from Zooplancton de sistemas acuáticos artificiales y naturales de Colombia. 1139 records from SWECO. 3756 records from Données naturalistes de Loïc SALAUN. 4034 records from nsmk_fish_biodiversity_2019. 3 records from A new species and new record of the genus Discoelius Latreille, 1809 (Hymenoptera Vespidae: Eumeninae) from China. 2172 records from EDP Foz Tua: Terrestrial Birds (transects) - Ecological Monitoring Program [2009-2012]. 460 records from Insectos recolectados en trampas Malaise en el departamento de Vichada - Proyecto Colombia Bio. 10275 records from EAC - Herbário Prisco Bezerra. 100 records from Euroants. 20333 records from Marine Biological Sample Database, JAMSTEC. 743 records from Insectos recolectados en trampas Malaise en el departamento de Antioquia - Proyecto Colombia Bio. 323 records from Otter (Lutra lutra), Outer Hebrides. 2592 records from Naturalis Biodiversity Center (NL) - Chelicerata and Myriapoda. 30 records from Ornitofauna de un Área Degradada por Actividad Minera en la Costa Caucana. 2 records from A new species of Hemacroneuria and additions to Chinoperla (Plecoptera: Perlidae) from China. 1078 records from Leif Richardson Vermont Bee Specimens. 9 records from PRA Sonneur à ventre jaune - étude de répartition. 3 records from A new genus and species of large-bodied caridean shrimp from the Crozet Islands, Southern Ocean (Crustacea, Decapoda, Lipkiidae) with a checklist of Antarctic and sub-Antarctic shrimps. 426 records from Données espèces - Expertise IQE 308. 410 records from Données espèces - Expertise IQE 95. 390 records from Collection Crustacea - ZMB. 416 records from The Living Murray Fish data. 422 records from Estudio herpetofaunístico de la Sierra Mazateca, Oaxaca, México. 4 records from Strepsiptera from Colombia: First record of the genus Strichotrema Hofeneder (Myrmecolacidae) and a new host-parasitoid association with Megalomyrmex cyendyra (Hymenoptera: Formicidae). 771 records from Monitoramento da taxocenose de anfíbios no Parque Nacional da Restinga de Jurubatiba. 4428 records from "Categorization of the wild food plants and their importance for primate development in the natural forest of Akpe (Lama) in southern Benin.". 1 records from A new species of Notosacantha Chevrolat (Coleoptera: Chrysomelidae: Cassidinae) from Timor-Leste with a key to the Notosacantha vicaria - group. 5 records from Cordulegaster virginiae sp. nov. from Mexico, including a comparison with C. diadema Selys, 1868, and a redescription of its larva (Odonata: Cordulegastridae). 1 records from The identification of the species of the ‘ Spilogona contractifrons species-group’ and the ‘ Spilogona nitidicauda species-group’ (Diptera, Muscidae) based on morphological and molecular analysis. 266 records from Structure of waterbird assemblages in fragmented coastal wetlands of Northeastern Algeria. 1 records from The crab spider genus Tarrocanus Simon, 1895 with notes on the genera Alcimochthes Simon, 1895 and Domatha Simon, 1895 (Araneae: Thomisidae). 20731 records from Long-term Bird Census in Cigu 2004-2017. 13 records from Three new species of Alburnoides from the southern Black Sea basin (Teleostei: Cyprinidae). 3 records from A new Hyphessobrycon (Characiformes: Characidae) of the Hyphessobrycon heterorhabdus species-group from the Central Amazon basin, Brazil. 9 records from Fatkullina imitata n. sp., second species of a unique cheilostome bryozoan genus with reversed-polarity zooidal budding, and new family Fatkullinidae. 21147 records from Carabidae records for Britain to 2014. 4 records from Polycentropus dinkinsorum (Trichoptera: Polycentropodidae), a newly described caddisfly species from the southern Appalachian Mountains, USA. 240 records from BARTH-Environnement_2017_12_18. 2 records from Schistura epixenos, a new species of loach from the Nakai Plateau, Laos (Teleostei: Nemacheilidae). 13 records from Four new species of the genus Trachelas L. Koch, 1872 and the first record of T. vulcani Simon, 1896 from South-West China (Araneae: Trachelidae). 15 records from Four new species and one new subspecies of Arctiinae (Lepidoptera: Erebidae) from the Tambopata river, Madre de Dios, Peru. 24 records from SNH Invertebrate Site Condition Monitoring 2013/14: Dollar Glen SSSI. 39 records from New records of sabellids and serpulids (Polychaeta: Sabellidae, Serpulidae) from the Tropical Eastern Pacific. 2707 records from SANBI: DNA Banking(1987-2011). 8 records from Review of the batfish genus Halicmetus Alcock, 1891 from Australian waters, with descriptions of two new species (Lophiiformes: Ogcocephalidae). 5 records from Phytoseiid mites of Slovenia (Acari: Mesostigmata): new records and first description of the male ofAmblyseius microorientalis. 226 records from Naturalis Biodiversity Center (NL) - Mammalia. 2654 records from Patrols activities and fixed transect data collections of the fauna of the W biosphere reserve of Benin of 2017. 1 records from New collections of freshwater crabs from northern Madagascar, with the description of a new species of Foza Reed & Cumberlidge, 2006 (Brachyura, Potamonautidae), and comments on their conservation status. 4 records from First records of Kempnyia and Macrogynoplax (Plecoptera: Perlidae) from Tocantins State, Brazil with description of the immatures and the adult female. 19 records from Description of lithologic section units of IODP Hole 325-M0035A. 1 records from A new Limnonectes (Anura: Dicroglossidae) from southern Laos. 4 records from Four new species of Rhyacophila Pictet 1834 (Trichoptera: Rhyacophilidae) from Southeast Asia. 3 records from Ghent university - Zoology Museum - Nematod Collection. 101 records from BIRDRACE Enger am Spektiv. 12 records from Sciapodinae from the Himalayan region with description of nine new species from Tibet (Diptera: Dolichopodidae). 6157 records from Données naturalistes de Julien BIRARD [Inventaire Eclair 18 juin]. 10 records from Données naturalistes de CLERGET sylvie. 2090 records from Regroupement de données "papillons menacés" collectées par les réseaux entre 1990 et 2012. 3 records from A new spider species, Heser stoevi sp. nov., from Turkmenistan (Araneae: Gnaphosidae). 7 records from Stadtrandlandschaft Apolda-Nord. 10 records from Annotated checklist of the Hemiptera Heteroptera of the Site of Community Importance and Special Area of Conservation “ Alpi Marittime ” (NW Italy). 2575 records from Meetnetten.be - Population counts for dragonflies in Flanders, Belgium. 45 records from Tejidos de los ejemplares colectados en la expedición al municipio de San Francisco, Cundinamarca - Caracterizaciones Humboldt. 80 records from Echinoderms occurence in a strongly contaminated Bay (Portman, Spain), using ROV and Scuba-diving surveys. 3 records from A new species of Alpheus Fabricius, 1798 (Decapoda: Caridea: Alpheidae) from the Caribbean coast of Panama. 1 records from BOTU-Fungi - Herbário Irina Delanova Gemtchújnicov - Coleção de Fungos. 5 records from A new species of Choroterpes Eaton, 1881 (Ephemeroptera: Leptophlebiidae) from India. 30924 records from Staffordshire Wildlife Trust Nature Reserves Inventory. 1 records from Nomenclatural changes in the planthopper tribe Hemisphaeriini (Hemiptera: Fulgoromorpha: Issidae), with the description of a new genus and a new species. 1 records from The identity of Cicinnus orthane Blanchard, 1852 (Lepidoptera, Mimallonidae, Cicinninae), type species of Cicinnus Blanchard, 1852. 1006 records from Herbarium specimens of Jardins botaniques and Conservatoire Botanique of Nancy (NCY). 23772 records from Chandeleur Island 2016 Amplicon Study Raw sequence reads. 1 records from Endemic Families of Madagascar. XIV. a New Restricted Range Species of Pentachlaena H. Perrier (Sarcolaenaceae) from Central Madagascar. 820 records from Banco de Germoplama del Jardín Botánico de Castilla-La Mancha. 31 records from Inventaire Faune. 1 records from MEXU/Tipos de plantas vasculares. 2 records from On the identity of Cyphonoxia maljuzhenkoi Zaitzev, 1928 (Coleoptera Scarabaeidae: Melolonthinae). 12202 records from Pelagic Gulf of Mexico Targeted loci environmental. 21 records from New state records and updated checklist of Aphodiini and Eupariini (Coleoptera: Scarabaeidae: Aphodiinae) from Mexico. 1 records from Redescription of Bomis larvata L. Koch, 1874 with the description of a new Australian species. 208 records from Registros de arañas en el marco del proyecto Influencia de la dieta sobre la toxinología y toxicología en arañas. 2835 records from Coral Reef Evaluation and Monitoring Project Florida Keys 2016. 1 records from Description of a new long-tailed skink (Scincidae: Trachylepis) from Angola and the Democratic Republic of the Congo. 2122 records from Données de Lépidoptères de Bruno DAUGET - Dépt de l'ALLIER (03). 3729 records from Condition of rocky reef communities around Tasmania: fish surveys, Australia (1992-1995 and 2006-2007). 7 records from Four new species of giant pill-millipedes from Vietnam (Sphaerotheriida, Zephroniidae). 201 records from Bulletin de la Société Linnéenne de Bordeaux, Tome 146 (N.S) n° 39 (4), 2011 - Données faune. 10 records from Bachpatenschaft Beeke. 89 records from BIRDRACE Hasenclevers Erben - NaBu-Bi-BirdRace-Open. 462 records from Données du/de la naturaliste Dodelin Benoît provenant de la base de donnée du SINP Île-de-France CETTIA. 64 records from Anfibios y reptiles del páramo de Sumapaz - Proyecto Colombia Bio. 1365 records from TPWD HARC Texas Coastal Fisheries Upper Laguna Madre Gill Net. 1265 records from Estado actual, identificación de riesgos y propuestas para el manejo de las especies invasoras presentes en las regiones hidrológicas prioritarias, confluencia de las Huastecas, Media Luna y Cabecera del río de La Laja. 5 records from Review of the genus Shilovia Makarchenko (Diptera: Chironomidae: Diamesinae Boreoheptagyiini) from the mountains of Central Asia, with morphological description and DNA barcoding of known species. 8 records from Illustrated identification key to the genera of New World Micrelytrini (Hemiptera: Alydidae: Micrelytrinae), with description of two new genera, one new species and new distributional records. 2 records from Sinopanamomus yunnanensis nov. gen. & nov. sp., a new genus and species of Leiestinae (Coleoptera, Endomychidae) from China. 5282 records from City of Edinburgh Natural Heritage Service - Bavelaw Marsh Bird Hide Records. 852 records from Observatoire des Mammifères marins de l'Archipel Guadeloupéen. Suivi Dauphins Les Saintes. 569 records from Spatial repartition of Antiaris toxicaria Lesch., Ceiba pentandra (L) Gaert, Terminalia superba Engl. & Diels and Triplochyton scleroxylon K. Schum. in Niaouli, Bonou, Pobe forests (South-Benin). 3357 records from marine metagenome. 1 records from The genus Toxoneura Macquart (Diptera, Pallopteridae) of the Oriental Region. 208 records from Données naturalistes de Daniel PAVON. 356 records from Coral Reef Evaluation and Monitoring Project Dry Tortugas 2008. 1 records from Modelaje de la distribución potencial de 10 especies de anfibios y reptiles en riesgo de extinción con escasos registros de presencia (ANONAU). 1998 records from Chronicle of Nature - Phenology of Plants of Carpathian Biosphere Reserve. 5 records from GBIF: Nova Scotia Museum of Natural History - Freshwater mussels. 1 records from On the taxonomy of the genus Pseudacronicta Kononenko, 2001 (Lepidoptera Noctuidae, Acronictinae): the identity of Acronicta omihsiensis Draeseke, 1928. 102 records from Données de la naturaliste Clélie Granger. 138 records from Database on reference specimens for medicinal plants of the Rubiaceae family, conserved at the CNARP herbarium. 525 records from Flora y fauna asociada al hábitat del Manatí antillano en la Ciénaga de Paredes, Magdalena Medio Santandereano. 3 records from Taxonomic noteson thegenusPseumenes Giordani Soika, 1935 (Hymenoptera: Vespidae Eumeninae) from Vietnam with key to all known species in the Oriental region. 220 records from Inventario de Mamíferos Mámbita. 1 records from Canadian Museum of Nature Mammal Collection. 2 records from A new morphologically cryptic species of Phyllomedusa (Anura: Phyllomedusidae) from Amazonian forests of northern Peru revealed by DNA sequences. 60 records from Caracterización de la fauna reptiliana asociada a la cuenca del río Atrato, para el estudio de su navegabilidad, Quibdó - Chocó, 2012. 17 records from Feuchtwiese am Nationalpark-Haus Neuwerk. 185803 records from Estonian Nature Observations Database. 13 records from New and little known species of Halolaelaps (Acari: Mesostigmata: Halolaelapidae) from Ukraine. 124 records from Birdrace-Die_Ackermännchen-Schalm-Eder-Kreis. 23 records from New record of the pentatomine stink bug species Caystrus orientalis Zhang and Lin (Hemiptera: Pentatomidae) from Japan. 24 records from The Xiphydria annulitibia group in northeastern Asia (Hymenoptera, Xiphydriidae). 3551 records from Estonian University of Life Sciences Institute of Agricultural and Environmental Sciences Mycological Herbarium. 2 records from Out on a limb: novel morphology and position on appendages of two new genera and three new species of ectoparasitic isopods (Epicaridea: Dajidae) infesting isopod and decapod hosts. 10 records from New plant associations for adults of some species of Acmaeodera Eschscholtz (Coleoptera: Buprestidae) occurring in the western United States. 928 records from MGC Herbarium of University of Malaga (Spain): MGC-Algae dataset. 27 records from Descriptions of four new species of Semia Matsumura (Hemiptera: Cicadidae: Psithyristriini) from Vietnam, with a key to the species of Semia. 8 records from Abundant box jellyfish, Chironex sp. (Cnidaria: Cubozoa: Chirodropidae), discovered at depths of over 50 m on western Australian coastal reefs. 11 records from Espèces envahissantes de la Guinée forestière extraites dans la base de données de CRRA Sérédou Macenta, IRAG.. 412 records from Helmintos parásitos de peces dulceacuícolas de cuencas hidrológicas del Centro-Norte de México (Durango). 275 records from Composición florística de áreas degradadas por actividad minera a cielo abierto en el municipio de Condoto-Chocó, como insumo para calcular la biomasa vegetal, 2017. 35953 records from MDFRC macroinvertebrate survey. 216 records from Données naturalistes de Pauline BALDUCCI. 82 records from Review of the Spirobolida on Madagascar, with descriptions of twelve new genera, including three genera of ' fire millipedes' (Diplopoda). 4074691 records from Swiss National Databank of Vascular Plants. 62 records from Amtsrain Apolda-Zottelstedt. 128 records from Inventaire des reptiles 2014. 15 records from PROJET DE CONSTRUCTION D’UNE ROUTE DE TRANSPORT DES MINERAIS DE BAUXITE DE GAC: EIES, inventaire des amphibiens (CESP2016-022). 11964 records from DIBA-Parc del Montnegre i el Corredor. 194 records from Données du/de la naturaliste LELARDOUX LOIC provenant de la base de donnée du SINP Île-de-France CETTIA. 69791 records from University of Tartu Natural History Museum and Botanical Garden Zooloogical Collections. 1 records from A new species of genus Oxytauchira from India (Orthoptera: Acrididae). 583 records from MoJ BioBlitz August 2018. 15492 records from Diversidad y dinámica del fitoplancton marino en la bahía de Acapulco, Guerrero. 1627 records from JRS Wetands data Rwanda, 2019. 31 records from Calcareous sponges of the Western Indian Ocean and Red Sea. 1 records from A new species of Polietina (Diptera: Muscidae) from South America, with an updated phylogeny of the genus and a review of species’ identity in GenBank. 326 records from Muséum_de_Toulon_et_du_Var_2017_12_18. 1134 records from EDP Baixo Sabor: Bat Roosts - Ecological Monitoring Program (PME) (2008-2014). 6 records from Redefinition of Nipponbathynella based on the four new species from East Asia (Crustacea: Bathynellacea: Parabathynellidae). 1993 records from Inventario de macroalgas de Isla Guadalupe, México. 53 records from Description of lithologic section units of IODP Hole 325-M0043A. 2788 records from Herbario de la Sociedad Micológica Barakaldo Mikologia Elkartea. 1 records from West Palaearctic species of the genus Diostracus Loew, 1861 (Diptera: Dolichopodidae). 1 records from Nesting biology and distribution of Stenancistrocerus (Paratropancistrocerus) obstrictus (Morawitz, 1895) (Hymenoptera: Vespidae: Eumeninae). 1 records from A new species of the swimming crab genus, Laleonectes Manning & Chace, 1990 (Crustacea: Brachyura: Portunidae), from the western Indian Ocean. 830 records from Invertebrados del Parque Nacional Arrecife Puerto Morelos. 8 records from Review of East Palaearctic species of Sympycnus Loew, 1857, with a key to species. 264 records from The Collection of Lichenicolous Fungi at the Botanische Staatssammlung München. 31 records from Colección de insectos de importancia médica del Instituto Nacional de Salud - Ceratopogonidae. 20440 records from Inventaire de la flore de Charente-Maritime 2017. 3 records from Prosoglypta, a new remarkable genus from Vietnam (Coleoptera: Staphylinidae: Omaliinae: Omaliini). 31 records from Caracterización Ecológica de los Macroinvertebrados de las Fuentes Hídricas presentes en el Cerro Jánano. 23 records from MCP - Coleção de Abelhas. 720 records from Données du naturaliste Bussac Augustin provenant de la base de donnée du SINP Île-de-France CETTIA. 306 records from Echinoderms in surface sediments off Sylt collected during HEINCKE cruise HE293. 135 records from Recensement des chiroptères 2012/2014 - Atlas de la biodiversité de Bordeaux Métropole. 3 records from Description of the previously unknown sexes in four West African Lycaenidae (Lepidoptera) with new data on their distribution. 1 records from Charinus rocamadre (Amblypygi, Charinidae): description of the female, ultrastructure of the male and female gonopods, and mitochondrial DNA sequences. 36 records from Taxonomic studies on potter wasps (Hymenoptera: Vespidae: Eumeninae) of south India. 4853 records from Inventaire des espèces végétales du sous bois des plantations de Teck de la forêt naturelle de la Lama. 983 records from DNA barcoding the fishes of Lizard Island (Great Barrier Reef). 402 records from SCFS - Sagehen Herbarium. 1 records from Eucharitidae new to the fauna of Saudi Arabia (Hymenoptera: Chalcidoidea), with the description of a new species and the previously unknown male of Eucharis (Psilogastrellus) albipennis Bouček. 2 records from New species and new geographical records in Disteniidae (Coleoptera, Chrysomeloidea) with revised keys to species of Novantinoe and American species of Distenia (Distenia). 19 records from Shrews of Poland. 181 records from Données du/de la naturaliste Beutin Sabine provenant de la base de donnée du SINP Île-de-France CETTIA. 2669 records from Données naturalistes de Pascal Dupont. 955 records from Woodmeadow Invertebrate Survey 2019. 124 records from K-State Museum of Entomological and Prairie Arthropod Research. 18 records from suivi du site Natura 2000 Carrière Saint Nicolas. 4 records from New distributional records and life stage description of Caenis species (Ephemeroptera: Caenidae) from Brazil. 2435 records from TPWD HARC Texas Coastal Fisheries Corpus Christi Bay Bag Seine. 2165 records from Inventaire des sangsues - détermination prélèvements de bureau d'études (qualité de l'eau) - Subvention UMS Patrinat. 310 records from Registros de macroinvertebrados acuáticos en un bosque seco del municipio de Honda. 3 records from A new species of the genus Larsia Fittkau (Diptera: Chironomidae) from India with cladistic analysis and a world key to the known males. 53 records from New Staphylinidae (Coleoptera) records with new collection data from New Brunswick, Canada. I. Aleocharinae. 212 records from (Table 2.2.2.1) Integrated abundance of sympagic meiofauna in sea-ice cores of Aurora Australis cruise SIPEX. 2 records from Wie viel Natur gibt es im Park?. 31 records from STELI 2015 Saint-Pée-sur-Nivelle (64) par l'association EcoGIS. 2 records from A new species of the fishfly genus Neochauliodes van der Weele (Megaloptera Corydalidae) from India. 598 records from Monitoreo de la abundancia, riqueza y biodiversidad de aves del Santuario de Flora y Fauna Galeras en 2019. 973 records from Freshwater Fishes of Bulgaria. 172 records from Données du/de la naturaliste Roquinarc'h Océane provenant de la base de donnée du SINP Île-de-France CETTIA. 600 records from Occurrence data of Birds of the Upper Tana Basin, Kenya. 29 records from Zootaxa. 10 records from Inventaire des Crustacés Décapodes de France métropolitaine. Données du compte CardObs 1113. 6762 records from Données du naturaliste MIGUET Pierre provenant de la base de donnée du SINP Île-de-France CETTIA. 1233 records from NBMB Herps. 140 records from Database on reference specimens for medicinal plants of the Fabaceae family, conserved at the CNARP herbarium. 12 records from A new species of Pimelodella Eigenmann & Eigenmann, 1888 (Siluriformes: Heptapteridae) from the Orinoco River basin. 67797 records from Microbial diversity in the Benguela coastal upwelling system as derived from 16S rRNA sequencing and RNA Stable Isotope Probing (SIP). 1 records from Description of the imago of Neocapritermes utiariti (Isoptera: Termitidae: Termitinae). 214 records from Caracterización de vertebrados terrestres en el Cerro Guadalupe, municipio de Manzanares. 434 records from Aves de Caño Cristales, La Macarena, Meta. 11131 records from Efectos del Cambio Ambiental en las comunidades de organismos de los ríos mediterráneos. 84 records from Marine algal (seaweed) flora of São Jorge Island, Azores. 2970 records from Distribution patterns of subtidal macrobenthos in the Tsitsikamma National Park. 26405 records from Données naturalistes de Monsieur François FOURNIER. 346 records from Birds and plant species near Petushki town (Vladimir region). 5 records from Sigambra sundarbanensis sp. nov. (Annelida, Pilargidae) from the Indian sector of Sundarbans Estuarine System, with remarks on parapodial glands. 358 records from NHMO DNA Bank Other groups collection. 238 records from Revues diverses et littérature grise.. 1 records from Five new species of Macrostomus Wiedemann and a checklist of Empididae (s. str.) (Diptera) from Bolivia. 28242 records from Naturhistorisches Museum Mainz, Feldbeobachtungsdaten Pflanzen. 9 records from Jeu de données convention FEGVE-SPN (numéro 2). 4 records from Two new species of the genus Deltomerodes Deuve, 1992 (Coleoptera, Carabidae, Patrobini) from Xizang, China. 6 records from Barsine insolita, a new species from Indochina and India (Lepidoptera, Erebidae, Arctiinae). 941 records from TPWD HARC Texas Coastal Fisheries Sabine Lake Gill Net. 28 records from DREAL_PACA_-_N2000_-_Pays_Provence_Verte_2017_12_18. 19 records from Schizorhynchia Meixner, 1928 (Platyhelminthes, Rhabdocoela) of the Iberian Peninsula, with a description of four new species from Portugal. 3 records from El género Aleuroparadoxus Quaintance y Baker 1914, con descripción de tres nuevas especies, nuevos registros y clave para las especies (Hemiptera: Aleyrodidae). 2 records from Contribution to the tribe Pentoffiini (Cicadellidae: Evacanthinae) with descriptions of two new species and the male of Evanirvana aurea Hill, 1973. 15 records from Description of lithologic section units of IODP Hole 325-M0050A. 522 records from Surface seawater carbonate chemistry, nutrients and phytoplankton community composition on a transect between North Sea and Arctic Ocean, 2008. 50 records from Lindesnes. 1404 records from Arthur Chapman Observations. 17 records from Damselflies of the genus Argia (Odonata: Coenagrionidae) from Ecuador with descriptions of five new species. 1 records from Contribution to the knowledge of Mediterranean lichen-feeding darkling beetles of the genus Stenohelops Reitter, 1922 (Coleoptera: Tenebrionidae). 571 records from Cuxhavener Küstenheiden. 3 records from Description of Bradinopyga konkanensis sp. nov. (Odonata: Anisoptera Libellulidae) from the coastal region of Maharashtra, India. 3806 records from University of Michigan Museum of Zoology, Division of Birds. 1160210 records from Hatikka Observation Database. 497 records from University of Wyoming Museum of Vertebrates (UWYMV) Bird Collection (Arctos). 751 records from Données naturalistes de Monsieur JOURDE Rémi. 811 records from Données naturalistes de AUNEAU Florent. 1806 records from uncultured marine picoeukaryote strain:Peuk_V4_NWP2 Raw sequence reads. 713 records from inatura - Erlebnis Naturschau Dornbirn. 3 records from Systematics of the Mesalina guttulata species complex (Squamata: Lacertidae) from Arabia with the description of two new species. 111 records from Birdrace-Uhulogen-Lippe. 2 records from Collection Aves (bird skins) SMF. 4 records from Revision of Arcastes Baly, 1865 from the Oriental Region (Coleoptera, Chrysomelidae, Galerucinae). 35 records from Revision of the stygobiont gastropod genera Plagigeyeria Tomlin, 1930 and Travunijana Grego & Glöer, 2019 (Mollusca; Gastropoda; Moitessieriidae and Hydrobiidae) in Hercegovina and adjacent regions. 17 records from Feral Pigs - Sightings and Cull records - 2018-2019. 27 records from Taxonomic revision of the genus Probolomyrmex Mayr, 1901 (Hymenoptera: Formicidae: Proceratiinae) for the Neotropical Region. 12 records from A new Bifidocoelotes species, with the description of the male of B. primus from Hong Kong, China (Agelenidae: Coelotinae). 1 records from First record of Gracixalus quyeti (Amphibia: Anura: Rhacophoridae) from Laos: molecular consistency versus morphological divergence between populations on western and eastern side of the Annamite Range. 7 records from DNA barcoding and morphological studies confirm the occurrence of three Atarbolana (Crustacea: Isopoda: Cirolanidae) species along the coastal zone of the Persian Gulf and Gulf of Oman. 1 records from A taxonomic review of the genus Gibbotettix with description of one new species (Orthoptera: Tetrigidae). 136 records from Birdrace-SpeedBirder-Zwickauer_Land. 83 records from Birdrace-Die_Vogelscheuchen-Herford. 9 records from Four new species of Plega Navás, 1928 (Neuroptera: Mantispidae) from Mexico. 2 records from Otter survey of Ireland 2004 & 2005. 2 records from Description of a new species of Liocheles Sundevall, 1833 (Hormuridae) from India. 3223 records from JOI - Herbário Joinvillea. 1 records from A new cryptic rock-dwelling Hemidactylus Oken, 1817 (Squamata: Gekkonidae) from northern Karnataka, India. 4 records from A revision of the African wolf spider genus Amblyothele Simon. 2370 records from Census of medical plant species of Benin (West Africa) by SOS Biodiversity. 84 records from BIRDRACE Vogelscheuchen. 5 records from A review of Smicronyx Schoenherr (Coleoptera, Curculionidae) of Israel, with description of two new species. 249 records from Données opportunistes produites par Alexandre RUFFONI dans le cadre de l’élaboration d’un guide de détermination des larves de plécoptères. 2 records from First record of the millipede genus Nesorthomorpha Jeekel, 1980 in Vietnam with description of a new species (Diplopoda, Polydesmida, Paradoxosomatidae). 81 records from Birdrace-Die_Ornithomaten-Herford. 5 records from Two new day-flying species of Agrotis Ochsenheimer (Lepidoptera: Noctuidae) from the alpine summit of the Maunakea Volcano. 123446 records from Suivi Temporel des Rhopalocères de France (STERF). 3 records from New species of the genus Mimogonia and Holotrochus from South America (Coleoptera: Staphylindae: Osoriinae). 3 records from Cellaria (Bryozoa, Cheilostomata) from the deep: new species from the southern Zealandian region. 917 records from Área Galeras - Monitoreo de Aves abril-octubre, 2018. 1 records from A new genus and species of Apameini (Lepidoptera: Noctuidae) from Sichuan (China). 856 records from NINA Vanndata fisk. 2 records from Sinibotia lani, a new species of botiid loach (Teleostei: Botiidae) from Guangxi, China. 1552 records from Microbial diversity in shallow water hydrothermal sediments of Gueishan Island, Taiwan. 510 records from Inventaires des cygnes du département de l'Eure. 23 records from Landwehrbach. 20 records from On the systematic status of Isopericlimenaeus Marin, 2012 and its type species, Periclimenaeus gorgonidarum (Balss, 1913) (Crustacea: Decapoda Palaemonidae). 25 records from Revision of freshwater shrimps belonging to Caridina weberi complex (Crustacea: Decapoda: Atyidae) from Polynesia with discussion on their biogeography. 25 records from Herpetofauna de la expedición Piedemonte Llanero - Proyecto Boyacá BIO UPTC. 61 records from Artenvielfalt in der Kinderakademie im RFZ. 96 records from Peces de la transición Andino-Amazónica del departamento del Caquetá - Proyecto Colombia BIO. 3 records from A new species and additional records of brachypterous Paederus (Coleoptera, Staphylinidae) of mainland China and Taiwan. 380 records from Herbario virtual bosques secos de Colombia - Sección herbario TULV (INCIVA). 295 records from Données de VINCENT Alexis (SAPROX). 1122 records from Vascular Plant Specimens of Yamagata Prefectural Museum. 1162 records from Avifauna de bosques nublados en la cordillera Occidental, departamentos del Valle del Cauca, Risaralda y sur de Antioquia.. 342 records from Glasgow Museums BRC: Chrysomelidae. 150 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México, segunda etapa 2008-2009 (Región sureste). 2 records from Contribution to the taxonomy of the paper wasp genus Polistes (Polistella) (Hymenoptera: Vespidae: Polistinae) from Vietnam, with description of a new species. 56 records from Données de la structure Forêts en Aulnoye provenant de la base de donnée du SINP Île-de-France CETTIA. 230880 records from Soil bacterial diversity is associated with human population density in urban greenspaces. 12 records from Two new species of the genus Laemostenus Bonelli sg. Antisphodrus Schaufuss from Turkey (Coleoptera: Carabidae: Sphodrini). 1 records from New taxonomic and faunistic data on Asian species of the genus Indenicmosoma Ardoin (Coleoptera: Tenebrionidae: Lagriinae), with description of a new species from Thailand. 1 records from Description of the larva of Meliboeus morawitzi (Semenov, 1905) (Coleoptera: Buprestidae). 39 records from USAC Mammals Collection. 471 records from Données du naturaliste Doux Yves provenant de la base de donnée du SINP Île-de-France CETTIA. 1462 records from Avifauna en dos parches de bosque seco del departamento del Valle Cauca (Colombia). 582 records from Données du naturaliste Christian Desmier. 2277 records from Stone-curlew Annual Surveys. 9 records from New species of Glossoscolex and Fimoscolex earthworms (Oligochaeta: Glossoscolecidae) from Embrapa Forestry, Paraná, Brazil. 810 records from The collection of Bathynellacea specimens of MNCN (CSIC) Madrid: microscope slices and DNA extracts. 97 records from Avifauna asociada a las fuentes abastecedoras de agua en La sierpe - Osbezcac (rio Saija, Timbiquí - Cauca). 836 records from Odoanta of Akwa Ibom State University, Nigeria. 21 records from Review of Lepidocyrtinus Börner, 1903 (Collembola, Entomobryidae, Seirinae): the African species. 1 records from A cladistic approach for generic delimitation of Paracloeodes Day, Rivudiva Lugo-Ortiz & McCafferty, and Varipes Lugo-Ortiz & McCafferty (Ephemeroptera: Baetidae). 830 records from Données naturalistes de Bernard Lalanne-Cassou. 5041 records from Données naturalistes de Franck NOEL. 420 records from Données de collection de l'inventaire des Papillons de jour de Martinique. 6 records from Review of the Oriental and Palaearctic bee fly genus Euchariomyia Bigot (Diptera: Bombyliidae: Bombyliinae). 2 records from A new Cnemaspis Strauch, 1887 (Squamata: Gekkonidae) from the northern Western Ghats, Maharashtra, India. 364 records from Natura 2000 ZPS Jarny - Mars-la-Tour. 12 records from New combinations, status, and species of Neotropical Ambrysini (Heteroptera: Naucoridae: Cryphocricinae). 258 records from Chronicle of Nature - Phenology of Birds of Darwin Nature Biosphere Reserve. 510 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Invertebrados. 13701 records from Inventaire et suivis d'espèces dans le Parc national des Cévennes. 6 records from Four new species of Scydmaeninae and Pselaphinae (Coleoptera: Staphylinidae) from Yunnan, China. 697754 records from SEWBReC Birds (South East Wales). 265 records from Luderbusch. 3406 records from NOAA National Coral Reef Monitoring Program Benthic Percent Cover. 82 records from Teich im Wald zwischen Böblingen und Schönaich. 807 records from Área Galeras - Monitoreo de Aves, 2016. 2 records from First record of Trissolcus basalis (Hymenoptera: Scelionidae) parasitizing Halyomorpha halys (Hemiptera: Pentatomidae) in the United States. 52 records from Review of Afrotropical Glenosema Kieffer (Hymenoptera, Bethylidae) with description of 13 new species. 7 records from DNA barcoding reveals a species group of the genus Campiglossa (Diptera, Tephritidae, Tephritinae) with recognition of a new species from East Asia and previously unknown females of Campiglossa coei (Hardy). 163 records from Zostera noltei seagrass meadows spatial distribution at LTER site Ria de Aveiro lagoon in 2014. 9 records from Resurrecting the genus Enitharoides Brooks, 1953 (Heteroptera: Nepomorpha: Notonectidae): description of three new species and redescription of Enitharoides brasiliensis (Spinola, 1837), comb. nov.. 1 records from Collection Echinodermata SMF. 5934 records from Agroforestry species in Parkia biglobosa's parklands in Northern Benin. 72960 records from Isle of Man wildlife records from 01/01/2000 to 13/02/2017. 4 records from A new species of large-bodied, tuberculate Hemidactylus Oken (Squamata: Gekkonidae) from the Eastern Ghats, India. 5018 records from Colección Entomológica del Programa de Biología - Universidad de Caldas (CEBUC). 61 records from Malawi-Cicindelidae-Biodiversity-Data. 3 records from Garra sindhi, a new species from the Jebel Samhan Nature Reserve in Oman (Teleostei: Cyprinidae). 3 records from A taxonomic review of the Korean species of the subgenus Datomicra Mulsant & Rey of the genus Atheta Thomson, with description of a new species (Coleoptera, Staphylinidae, Aleocharinae). 19 records from Cethosia myrina butterfly specimens at Museum Zoologi Bogor, Indonesia. 1 records from MEXU/Flora de Oaxaca. 14075 records from Vertebrate Zoology Division - Herpetology, Yale Peabody Museum. 128 records from Scleractinia specimens of Kuroshio Biological Research Foundation. 625 records from Données araignées de Corse par Canard A., Rollard C., Villepoux O.. 19780 records from Eulachon migration bottom trawl surveys. 1 records from A new species of king cricket Glaphyrosoma Brunner von Wattenwyl, 1888 (Orthoptera: Anostostomatidae: Glaphyrosomatini) from Costa Rica with behavioral observations. 655 records from Nonindigenous Aquatic Species (NAS) Database Non-freshwater Specimens. 2082 records from Registros biológicos de flora para el desarrollo de acciones de evaluación, seguimiento y monitoreo en los elementos priorizados de la estructura ecológica principal del distrito capital. Bogotá D.C.. 6 records from Arizona State University Lois B. O'Brien Collection. 9741 records from marine sediment metagenome Raw sequence reads. 583 records from Herbario virtual bosques secos de Colombia - Sección herbario TOLI (UT). 113 records from The pholcid spiders of Sri Lanka (Araneae: Pholcidae). 3 records from Taxonomic notes on the tribe Dryptini Bonelli, 1810 with description of a new genus and species from China (Coleoptera: Carabidae: Dryptini). 1571 records from Chronicle of Nature - Phenology of Plants of State Nature Reserve Olekminsky. 3 records from Three new taxa of Noctuidae from China (Lepidoptera: Noctuidae). 14568 records from Arizona State University Hasbrouck Insect Collection. 28 records from Description of lithologic section units of IODP Hole 325-M0055A. 184 records from Chronicle of Nature - Phenology of Plants of Kronotsky Federal Nature Biosphere Reserve. 2536 records from Invasive Alien Species Occurrence in Ghana. 232 records from Insectos en el municipio de San Juanito, Meta - Colombia BIO. 165 records from Registros de quirópteros de tres localidades del caribe colombiano. 1015 records from Inventario ictiofaunístico de los humedales de Puerto Morelos, Quintana Roo. 715 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase (Herpetológica Chetumal). 1 records from On the Neotropical spider genus Tullgrenella Mello-Leitão, 1941: two new species complementary descriptions and new records (Araneae: Salticidae). 189 records from Naturpark Sternberger Seenland. 1 records from New species of deep-water Calcigorgia gorgonians (Anthozoa: Octocorallia) from the Sea of Okhotsk, with a re-diagnosis and a taxonomic review of the genus. 4335 records from Eastern offshore environmental monitoring of Krishna Godavari Basin Bay of Bengal 2013-2016, Funded by: ONGC India. 1 records from Description of three new velvet geckos (Diplodactylidae: Oedura) from inland eastern Australia, and redescription of Oedura monilis De Vis. 1599 records from Inventaire des bois par espèce végétale de la forêt classée de Ziama en Guinée Forestière (BID-AF2015-0066-REG). 5 records from Description of a new species of Moenkhausia (Characiformes: Characidae) from the upper Paraguay basin, Central Brazil, with comments on its phylogenetic relationships. 2482 records from NCSM Mammalogy Collection. 11 records from Taxonomic review of Epicadinus Simon, 1895 (Araneae: Thomisidae). 11 records from Taxonomy of Paraplatyarthrus Javidkar and King (Isopoda: Oniscidea: Paraplatyarthridae) with description of five new species from Western Australia, and comments on Australian Trichorhina Budde-Lunde, 1908 (Platyarthridae). 2 records from Peripus, a new genus of Xanthopygina (Coleoptera: Staphylinidae) from South America. 1014 records from DMNS Parasite Collection (Arctos). 56 records from Chronicle of Nature - Phenology of Insects of Kaniv Nature Reserve. 91 records from GEO-Tag mit der NAJU des Landkreises Ahrweiler am Bausenberg. 1 records from Biology and population studies of two endemic orchid species on sub-Antarctic Macquarie Island. 122 records from Inventaire de la Flore patrimoniale dans la RNN Etang de Saint-Paul avant le 31/12/2017. 171 records from Fungal Bioblitz in Białowieża Primeval Forest at 18th Congress of European Mycologists. 1 records from Swedish Malaise Trap Project (SMTP) - Mymar. 4292 records from Données naturalistes de Matthias COLIN. 6781 records from Colección general del plantas vasculares del Herbario JBB. 42293 records from Colección de Entomología del Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-E). 144559 records from Species data for Scottish waters held and managed by Scottish Natural Heritage, derived from benthic surveys 1993 to 2018. 2 records from Taxonomic note on the oil-collecting bee Centris dimidiata (Olivier, 1789) (Hymenoptera: Apidae: Centridini). 2 records from Cowan Tetrapod Collection - Herpetology. 1 records from The invertebrate host of salmonid fish parasites Ceratonova shasta and Parvicapsula minibicornis (Cnidaria: Myxozoa), is a novel fabriciid annelid, Manayunkia occidentalis sp. nov. (Sabellida: Fabriciidae). 4 records from Taxonomic update of the Neotropical genus Cryptocladocera Bezzi, 1923 (Diptera: Tachinidae), with remarks on tachinids with fissicorn antennae. 24851 records from CSIC-Real Jardín Botánico-Colección de Plantas Vasculares (MA). 2 records from The discovery and description of a new species of Bent-toed Gecko of the Cyrtodactylus pulchellus complex (Squamata: Gekkonidae) from the Langkawi Archipelago, Kedah, Peninsular Malaysia. 12454 records from SPC NECTALIS Zooplankton/Micronekton specimens, New Caledonia 2014. 210834 records from DFO Pacific Groundfish Synoptic Trawl Surveys - Hecate Strait. 6 records from New records, new genera, and new species in Acanthocinini (Lamiinae) from the Neotropical region, and new synonym in Cerambycinae (Coleoptera, Cerambycidae). 1 records from Sinoperlodes, a new genus of subfamily Perlodinae (Plecoptera, Perlodidae) from coastal southeastern China. 17 records from New species of Duplominona Karling, 1966 (Platyhelminthes, Proseriata) from the Pacific coast of Panama. 105 records from Royal Belgian Institute of Natural Sciences Mammal collection. 3 records from Eleven new species and a new country record of Pselaphodes (Coleoptera: Staphylinidae: Pselaphinae) from China, with a revised checklist of world species. 31 records from Registros de mamíferos de los Parques Ecológicos Distritales de Montaña de Bogotá, D.C.. 11 records from Description of a new species of Loxosceles Heineken & Lowe (Araneae, Sicariidae) recluse spiders from Hidalgo, Mexico, under integrative taxonomy: morphological and DNA barcoding data (CO 1 + ITS 2). 21 records from Digitalización y sistematización de las colecciones biológicas del INECOL (Xiloteca). 21640 records from Fife Nature Records Centre combined dataset. 93 records from First records of 31 species of butterflies and moths (Lepidoptera) in Cameroon, with remarks on their elevational ranges. 5 records from Notes on the genus Kosmiomiris Kirkaldy (Hemiptera: Miridae: Hyalopeplini) with description of a new species. 103 records from A monograph of the genus Maladera Mulsant & Rey, 1871 of China (Coleoptera: Scarabaeidae: Melolonthinae: Sericini). 2 records from Annotated checklist of the false blister beetles (Coleoptera: Tenebrionoidea: Oedemeridae) from Iran. 2 records from Two new species of the spider genus Pholcus Walckenaer, 1805 (Araneae, Pholcidae) from Tajikistan, with the first description of female Pholcus sidorenkoi Dunin, 1994. 5 records from New taxa and notes on crickets of the subfamily Landrevinae (Orthoptera: Gryllidae) from Brunei Darussalam, Borneo. 50 records from CHAS Botany Collection (Arctos). 1 records from First record of Gauguin's blunt-nose lizardfish, Trachinocephalus gauguini Polanco, Acero & Betancur 2016 (Teleostei: Synodontidae) outside the Marquesas Archipelago. 5 records from New records of species of the Polyonyx sinensis group (Crustacea: Decapoda: Anomura: Porcellanidae) from Japan, the Philippines, Singapore, and Malaysia, with descriptions of two new species. 237 records from Avifauna asociada a humedales urbanos del municipio de Quibdó - Chocó, 2019. 3 records from Description of a new species of Music frogs (Anura, Ranidae, Nidirana) from Mt Dayao, southern China. 7 records from A new species of the genus Goera Stephens (Trichoptera, Goeridae) found in madicolous habitats in Amami-Oshima, southwestern Japan. 1964 records from Institut Botanic de Barcelona (IBB-CSIC-ICUB), BC-Lichen. 3 records from jamaica_invasive_alien_species. 10 records from Integrative taxonomy reveals cryptic diversity in neotropical grasshoppers: taxonomy, phylogenetics, and evolution of the genus Sphenarium Charpentier, 1842 (Orthoptera: Pyrgomorphidae). 8 records from Two new deep-water species of the genus Thorogobius (Teleostei: Gobiidae) from the upper continental slope of the Eastern Central Atlantic. 5 records from Hiding in plain sight: rediscovery and review of Parygrus Erichson, 1847, with description of five new species from the Neotropics (Coleoptera: Byrrhoidea Dryopidae). 277 records from Programme de valorisation des zones humides chassées - volet Oiseaux. 3 records from A new species of the spider genus Phlogiellus (Araneae, Theraphosidae) from Hainan, China. 1 records from A new tardigrade species of the genus Neostygarctus Grimaldi de Zio et al., 1982 (Tardigrada, Arthrotardigrada) from the Great Meteor Seamount, Northeast Atlantic. 270 records from BIRDRACE Niederlausitz-Team. 48 records from Scorpiones Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 441 records from Línea base del medio biótico en los bosques dentro de la zona propuesta para Acuerdos de Conservación Voluntaria en la microcuenca de la Quebrada Aguazula - Rincón del Soldado_Yopal. 1319 records from Inventaire et suivi Avifaune. 34 records from Two new species of Tipula (Vestiplex) Bezzi (Diptera, Tipulidae) from Northwest China. 459 records from Marine Mammal Observation - Total Denmark 2013-2020. 6117 records from Invasive species - Chinese mitten crab (Eriocheir sinensis) in Flanders, Belgium. 61 records from Chronicle of Nature - Phenology of Birds of Ilmensky State Nature Reserve, Russian Academy of Sciences, Urals Branch. 6 records from A new species of Notacanthurus Tshernova, 1974 (Ephemeroptera: Heptageniidae) from India. 3 records from A new species of Isoperla (Plecoptera: Perlodidae) from the Qinling Mountains of northwestern China and notes on the Chinese species of the genus. 2 records from A new macromedusa from the coast of Mozambique: Aurelia mozambica sp. nov (Scyphozoa: Ulmaridae). 10 records from SNH Invertebrate Site Condition Monitoring of Beetle Assemblage Features 2015: Taynish Woods SSSI. 38 records from Fish Fauna of Berlin. 11193 records from Baselines Initiative 16S rRNA gene dataset: Baselines Amplicon Release 1 (R1) Caribbean Sea near Curacao (including saline pond samples in Curacao) 2015. 5 records from Five new species of the spider genus Pholcus Walckenaer, 1805 (Araneae: Pholcidae) from China and Thailand. 4 records from King penguin census data, Gadget Gully, Macquarie Island (1993-2008). 6 records from Two new species of the spider genus Wanniyala Huber & Benjamin, 2005 (Araneae Pholcidae) from Sri Lanka. 2 records from Discovery of a new species of Lacon Laporte (Coleoptera: Elateridae: Agrypninae) endemic to Cyprus, with a modified tarsal morphology. 3391 records from Kherson State University herbarium (KHER), Department of Botany. 206 records from Colección de Herpetología del Instituto de Ciencias Naturales (ICN-MHN-Her). 7 records from Contribution to the knowledge of Cloeodes Traver 1938 (Ephemeroptera, Baetidae). 624 records from Inventaire des Coléoptères Longicornes des Antilles françaises. 1444 records from Nijmegen Natural History Museum (NL) - Herbarium. 38 records from The Sphecid wasps of the genus Cerceris LATREILLE, 1802 of the " Biologiezentrum Linz " - Collection in Linz, Austria, from Subsaharan Africa and Madagascar, with description of five new species (Hymenoptera, Apoidea, Crabronidae). 24 records from 2019_nsmk_smpl_ms_20200603. 1 records from Two new species of amphipods (Crustacea: Amphipoda: Photidae) from Korean waters with a redescription of Gammaropsis longipropodi. 3 records from Morphological and ecological convergence at the lower size limit for vertebrates highlighted by five new miniaturised microhylid frog species from three different Madagascan genera. 938099 records from Estonian Naturalists’ Society. 952095 records from Suffolk Biodiversity Information Service (SBIS) Dataset. 2 records from Three new species of Synagelides Strand, 1906 from China (Araneae: Salticidae). 124922 records from DEEPEND: Microbiome and bacterioplankton rRNA gene sequence data collected from Gulf of Mexico seawater samples. Cruises DP03 and DP04 from Jan 2016 - December 2016. 1 records from Helmutneris vadum, a new species of Lumbrineridae (Annelida) from Lizard Island, Great Barrier Reef, Australia. 34 records from Sideritis syriaca subsp. nusairiensis and Thymus sipyleus in Mount Lebanon. 82 records from Les aires de plus grand intérêt patrimonial pour les ptéridophytes dans l'étage des forêts sempervirentes saisonnières tropicales à la Martinique. 105 records from Données rhopalocères 2014/2015 des Mattes de Paladon. 954 records from Département_du_Var_2017_12_18. 191 records from sediment microorganism Metagenome. 27 records from Schulgarten Waldorfschule Hassfurt. 127 records from Wildlife Observations Bardon Hill 31.5.09. 135 records from http://www.geo-artenvielfalt.de (www.geo-artenvielfalt.de) - Birdrace-Pody&Co.-Plön. 9 records from Phenological Center - Mushrooms (Laplandskiy). 25 records from Revision of the squat lobsters of the genus Leiogalathea Baba, 1969 (Crustacea, Decapoda, Munidopsidae) with the description of 15 new species. 2 records from Tropiorhynchus annandalei (Coleoptera: Scarabaeidae: Rutelinae), a new species from Maharashtra, India. 2 records from A new deep-sea Cirripedia of the genus Heteralepas from the northeastern Atlantic. 3455 records from permafrost metagenome Targeted loci environmental. 3 records from Two new species of Sabellariidae (Annelida, Polychaeta) from the abyss of eastern Australia. 8016 records from University of Alberta Vascular Plant Herbarium (ALTA-VP). 1 records from A new western Canadian record of Epeoloides pilosulus (Cresson). 3137 records from CTD water column metabarcoding. 720 records from A species-level taxonomic review and host associations of Glyptapanteles (Hymenoptera, Braconidae, Microgastrinae) with an emphasis on 136 new reared species from Costa Rica and Ecuador. 318 records from Revision of Chondrocyclus s. l. (Mollusca: Cyclophoridae), with description of a new genus and twelve new species. 1 records from Eusocial wasp fauna of Sulawesi Island, the central island of Wallacea (Hymenoptera: Vespidae; Polistinae, Vespinae). 59 records from A new species of habitat – forming Suberites (Porifera, Demospongiae, Suberitida) in the Benguela upwelling region (South Africa). 2 records from Two new species of Petrobunus from China (Opiliones: Laniatores: Petrobunidae). 4 records from A new medium-bodied rupicolous Hemidactylus Goldfuss, 1820 (Squamata Gekkonidae) from the Sirumalai massif, Tamil Nadu, India. 1 records from The identity of the invasive yellow-striped terrestrial planarian found recently in Europe: Caenoplana variegata (Fletcher & Hamilton, 1888) or Caenoplana bicolor (Graff, 1899)?. 55 records from SNH Invertebrate Site Condition Monitoring 2015: Rinns of Islay SSSI. 11665 records from CeDoc de Biodiversitat Vegetal: BCN-Cormophyta. 1 records from Données naturalistes de REYJOL Yorick. 286 records from Registros de almeja (Polymesoda arctata) en la Ciénaga de pajarales. 13 records from Two new genera and five new species of Mugadina - like small grass cicadas (Hemiptera: Cicadidae: Cicadettini) from Central and Eastern Australia: comparative morphology, songs, behaviour and distributions. 14 records from On the genus Tylorida Simon, 1894 with the first record of the genus Atelidea Simon, 1895 from India (Araneae: Tetragnathidae, Leucauginae). 4 records from A new species of the genus Urumaelmis Satô (Coleoptera, Elmidae, Macronychini) from Kyushu Island, Japan. 1 records from Redescription of Chrysidea pumiloides Zimmermann, 1956, and description of three new species of Chrysidea from Madagascar (Hymenoptera: Chrysididae). 239 records from Colección de reptiles del Museo de Historia Natural de la Pontificia Universidad Javeriana. 9639 records from Diatomeas (Bacillariophyceae) y dinoflageladas (Dinophyceae) frecuentes en el Pacífico mexicano (costa oeste de Baja California, Pacífico centro y sur). 1 records from A new species of Allomallodon Santos-Silva and Galileo, 2010 from Bolivia (Coleoptera: Cerambycidae: Prioninae: Macrotomini). 6 records from Two new species of Corumbataia (Hypoptopomatinae: Loricariidae) from Rio Corrente, upper Rio Paraná basin, Brazil. 1 records from Suphisellus grossoi sp. n., a new burrowing water beetle from South America and notes on S. flavolineatus (Régimbart, 1889) and S. grammicus (Sharp, 1882) (Coleoptera: Noteridae). 2 records from Four species of Tubifex Lamarck (Annelida: Oligochaeta: Naididae) from Tibet, China. 1 records from Taxonomic and nomenclatorial revision within the Neotropical genera of the subtribe Odontocheilina W. Horn in a new sense— 18. Six Mexican and Central American species related to Odontocheila mexicana Laporte de Castelnau and O. ignita Chaudoir, with a description of O. potosiana sp. nov.. 4 records from The genus Spirontocaris Spence Bate, 1888 (Caridea, Decapoda, Thoridae) in western Mexico. 9 records from Inventario Herpetológico Pauto M, La Primavera, Yopal, Casanare. 95 records from Megafauna of the UKSRL exploration contract area and eastern Clarion-Clipperton Zone in the Pacific Ocean: Annelida, Arthropoda, Bryozoa, Chordata, Ctenophora, Mollusca. 203 records from Estrategia de conservación de grandes felinos en el departamento del Meta. 129 records from BIRDRACE Oostfreesland Bird-Lopers. 3 records from Parochodaeus bituberculatus (Erichson) (Coleoptera: Ochodaeidae) and Faargia gentilii (Martínez) (Coleoptera: Scarabaeidae), two species newly discovered in Chile. 238 records from Données Mammifères marins Aquasearch - Dauphin Passion. 4 records from A new species of freshwater crab of the genus Phallangothelphusa Pretzmann, 1965, from the foothills of the Serranía Yariguíes of Colombia (Crustacea: Decapoda: Pseudothelphusidae). 1 records from A new blind snake of the genus Letheobia (Serpentes: Typhlopidae) from Rwanda with redescriptions of L. gracilis (Sternfeld, 1910) and L. graueri (Sternfeld, 1912) and the introduction of a non-invasive preparation procedure for scanning electron microscopy in zoology. 1 records from First description of the male of Glyphiulus formosus (Pocock, 1895) (Diplopoda Spirostreptida: Cambalopsidae) from China. 1459 records from Coral Reef Evaluation and Monitoring Project Florida Keys 2009. 1 records from Redescription and biology of Gonatopus amazonicus Olmi (Hymenoptera, Dryinidae) from Southern Brazil. 31 records from Bulletin d'informations de l'Association française de Lichénologie. 3 records from A checklist of seed-beetles (Coleoptera: Chrysomelidae: Bruchinae) from Iran. 2 records from Two new species of Sinacroneuria Yang & Yang, 1995 (Plecoptera: Perlidae) from Guizhou, southwestern China. 213 records from Tejidos de especimenes colectados en la ventana de biodiversidad Río Guamués, corregimiento El Encano, Municipio de Pasto, Nariño, Colombia. 11 records from Occurrence Data of Small Carnivores (Mammalia, Carnivora) in the National Museums of Kenya Zoology Collection. 13 records from A review of the genus Orionis Shaw (Hymenoptera: Braconidae: Euphorinae) and first records of the genus from South America and the Oriental Region. 58 records from Capercaillie national surveys. 1 records from Description of two new Homoeocera Felder from Guatemala and Mexico (Lepidoptera, Arctiidae, Arctiinae, Euchromiini). 267 records from La familia Asteraceae en México. Fase VI. 505 records from (Table 3) Protist occurrence in bottom sea ice and surface water samples obtained during a CCGS Amundsen cruise in 2007/2008. 830 records from Regroupement de données Odonates et Lepidotères. 949 records from WTSWW Data: All Taxa (West Wales). 56 records from EDP Foz Tua Nocturnal Birds - Ecological Monitoring Program [2011-2017]. 51729 records from Cartografía de vegetación a escala de detalle 1:10.000 de la masa forestal de Andalucía. 128 records from Données espèces - Expertise IPE 10. 48 records from Marine gastropod distribution from patagonian shallow waters. 192 records from "Ahrschleife bei Altenahr". 3 records from Salticidae (Arachnida: Araneae) of New Caledonia: Genus Corambis Simon, 1901. 9 records from A new species of Leuctra from Turkey, and notes on Anatolian Rhabdiopteryx (Plecoptera: Leuctridae & Taeniopterygidae). 28579 records from South Australian Museum Australia provider for OZCAM. 2 records from Two new Thiratoscirtus species from Gabon (Araneae, Salticidae, Thiratoscirtinae). 1 records from Documenting diversity in the Amazonian butterfly genus Bia (Lepidoptera, Nymphalidae). 5 records from Twenty more new species of Agrilus (Coleoptera: Buprestidae: Agrilinae) from the Oriental region. 1 records from Brock University Herbarium (BU). 15 records from New species of Otiothopinae (Araneae: Palpimanidae) from Colombia. 13718 records from SIO Benthic Invertebrate Collection. 13 records from The genus Anacroneuria Klapálek, 1909 (Plecoptera: Perlidae) from Maranhão State, northeastern Brazil. 279 records from DASSH Data Archive Centre volunteer survey data. 405470 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Aves Reproductoras. 2885 records from Bases ecológicas y sociales para la conservación y el manejo de las abejas sin aguijón en Oaxaca, México. 865 records from Biodiversidad vegetal de la parte alta oeste de la cuenca del Chuviscar, Chihuahua. 69 records from Unter hellen Zinnen und finsteren Grotten. 490 records from Insectos de la expedición en el páramo de Ocetá, Boyacá - Proyecto Boyacá BIO. 10167 records from Observaciones de Aves asociadas a investigaciones de la Univerisdad ICESI en el periodo 2014-2019. 121 records from BIRDRACE Immerwiederhopf. 1 records from An annotated taxonomic checklist of the Neotropical Gracillariidae (Lepidoptera) with links to the information on host plants and parasitoids. 47 records from New species and records of deep-water Orbiniidae (Annelida, Polychaeta) from the Eastern Pacific continental slope, abyssal Pacific Ocean, and the South China Sea. 2 records from A taxonomic revision of the Western Palaearctic genus Cacochroa Heinemann 1870 (Lepidoptera, Depressariidae, Cryptolechiinae) with description of a new genus and a new species. 9 records from Integrative taxonomy resuscitates two species in the Lasioglossum villosulum complex (Kirby, 1802) (Hymenoptera: Apoidea: Halictidae). 6281 records from Modernisation des ZNIEFF du PnrL. 1 records from A review of Garra (Teleostei: Cypriniformes) from two rivers in West Yunnan, China with description of a new species. 3 records from A new species of the emesine assassin bug genus Emesopsis (Hemiptera: Heteroptera: Reduviidae) from Vietnam. 37 records from Caracterización de Reptiles de las lagunas del municipio del Medio Baudó. 601 records from Muestreos y recolectas de flora endémica y casi-endémica de matorral costero y chaparral de la zona mediterránea Baja California, México. 50 records from Données d'observation de phanérogames marines en Martinique. 1264 records from Grand Voyeux - Suivis scientifiques. 34 records from Eight new species of the genus Anaplecta Burmeister, 1838 (Blattodea: Blattoidea: Anaplectidae) from China based on molecular and morphological data. 18 records from Taxonomic revision of the genus Prionopelta Mayr, 1866 (Formicidae: Amblyoponinae) for the Neotropical region. 17 records from New species and records of the supertribe Stomatosematidi (Diptera: Cecidomyiidae) in Brazil. 41 records from UWIZM Cnidarians. 299 records from Colección Taxonómica Nacional de Insectos “Luis María Murillo” (CTNI). 374 records from Coastal and Marine Species Database. 31219 records from NEON Biorepository Carabid Collection (Pinned Vouchers). 900 records from Convention Fédération française de golf - MNHN 2016-2019.. 59847 records from Tasmanian Museum and Art Gallery provider for OZCAM. 54 records from Weidegebiete in der Selzrenaturierung. 2277 records from Bacterial community dynamics during polysaccharide degradation at contrasting sites in the Southern and Atlantic Oceans. 209 records from Données du naturaliste DESCHATRE Thierry provenant de la base de donnée du SINP Île-de-France CETTIA. 22 records from Avifauna de los bosques húmedos y remanentes de Tierralta - Córdoba, 2011. 1 records from A new large and colourful species of the genus Doto (Nudibranchia: Dotidae) from South Africa. 1365906 records from Liste des espèces de la faune sauvage de la base de données naturalistes Faune-France 2018.. 740 records from Monitoring data of marine turtles on the Togolese coast over 2012-2013 years. 4575 records from Narragansett Bay, RI Sediments Targeted Locus (Loci). 3 records from A new species of Mada Gordon from the Andes (Coleoptera: Coccinellidae: Epilachnini). 1811 records from Point Count Data for TIDE's Private Land (Kern), Belize 2009-2013. 1246 records from NEON Biorepository Mammal Collection (Vouchers [Standard Sampling]). 45 records from Brown bear monitoring data from Deosai National Park. 296 records from Colección de Boraginales y Brassicaless del Museo Botánico CORD - IMBIV. 4 records from A review of Gonothrombium Feider, 1950 (Actinotrichida: Microtrombidiidae) with description of a new species from Turkey. 54966 records from Zoologische Staatssammlung Muenchen - International Barcode of Life (iBOL) - Barcode of Life Project Specimen Data. 79 records from Etude d'état initial de la biodiversité dans le cadre des EIES sur les plateaux situés dans la zone sud (Pompo) de la concession minière de Guinea Alumina Corporation(GAC) dans la region de Boké (CESP2016-022). 1 records from A new species of Anthiadinae (Teleostei: Serranidae) from São Pedro and São Paulo Archipelago, Brazil, Equatorial Atlantic.. 2 records from Modelación de la distribución potencial del género Bursera (Burseraceae) en México. 15181 records from FLOR - Herbário do Departamento de Botânica da Universidade Federal de Santa Catarina. 936 records from Alterra (NL) - Microarthropods inventory in Dune vegetation. 67 records from Einen Tag lang Forscher sein - Die 5c der Erich-Kästner-Schule erforscht das Bachemer Wiesental. 1 records from Pseudolycoriella skusei sp. nov. (Diptera: Sciaridae), a new dark-winged fungus gnat from Norfolk Island and Australia. 3704 records from Inventaire des pelouses calcicoles du PNR du Marais Poitevin 2017. 1066 records from Territorial Andes Occidentales - Densidad poblacional VOC subsistema cámaras trampa, 2018. 23 records from Systematics of the enigmatic South American Streblopus Van Lansberge, 1874 dung beetles and their transatlantic origin: a case study on the role of dispersal events in the biogeographical history of the Scarabaeinae (Coleoptera: Scarabaeidae). 858 records from Registros biológicos asociados al monitoreo de la diversidad de escarabajos en paisajes ganaderos silvopastoriles - Unillanos 2019. 4306 records from Saproxylic and herbivorous beetle species in old near-natural and old managed forests in south-eastern Norway. 227 records from Data on cetacean strandings (1999 - 2014) on the Ukrainian coast of the Black Sea and the Sea of Azov and adjoining areas. 1 records from Two new species of the bamboo-feeding planthopper genus Arcofacies Muir (Hemiptera: Fulgoroidea: Delphacidae) from China. 15 records from MFS-Plantulas - Herbário Profª. Drª. Marlene Freitas da Silva - Coleção de Plântulas. 59 records from Tree-dwelling ant survey (Hymenoptera, Formicidae) in Mitaraka, French Guiana. 1 records from Two deep-sea decapod crustaceans collected off eastern Hokkaido, Japan: Sclerocrangon rex n. sp. (Caridea: Crangonidae) and Munidopsis verrilli Benedict, 1902 (Anomura: Munidopsidae). 1611 records from Registros Primates Neotropicales Convocatoria APC. 233 records from Borstgrasrasen um die Burg Baldenau im Oberen Dhrontal. 7 records from New species of Clavigeritae (Coleoptera: Staphylinidae: Pselaphinae) from Malawi and South Africa. 6 records from Review of the genus Promalactis Meyrick, 1908 (Lepidoptera: Oecophoridae) III. The trilineata species group, with descriptions of four new species. 31 records from Swedish Malaise Trap Project (SMTP) - Pimplinae. 631 records from Anammox bacteria in sediment cores of Daya Bay, China. 1 records from Off the scale: a new species of fishscale gecko (Squamata: Gekkonidae: Geckolepis) with exceptionally large scales. 11 records from Six new species of Macellicephala (Annelida: Polynoidae) from the Southern Ocean and south Atlantic with re-description of type species. 2 records from Potamocloeon edentatum sp. n. from Usambara Mountains in Tanzania (Ephemeroptera, Baetidae). 1646 records from HJ herbarium - Universidade Federal de Goiás - Unidade Jataí - Herbário Virtual REFLORA. 1 records from Systematics, Morphology and Biogeography Phylogeny of the Augochlora clade with the description of four new species (Hymenoptera, Apoidea). 1337 records from Mollusques dulcicoles de France - Jacques MOUTHON. 50 records from Antractic whale observation on a platform of opportunity abroad krill fishing vessel "Dalmor II", April - July 2011.. 303 records from BID-Malawi-Geometridae-Biodiversity-Data. 396 records from Inventaire et suivi odonate/Fadet des laîches des sites Natura2000 ‘Zones humides de l’étang de Léon’ et ‘Zones humides de l’arrière dune du Marensin’. 2 records from The freshwater shrimp family Euryrhynchidae Holthuis, 1950 (Crustacea: Decapoda: Caridea) revisited, with a taxonomic revision of the genus Euryrhynchus Miers, 1878. 55 records from Diversidad de ocho grupos de insecta (Odonata, Lycidae, Phengodidae, Lampyridae, Cantharidae, Cerambycidae, Syrphidae y Vespidae) en tres regiones con bosque tropical caducifolio en México. 2 records from First description of male of the type species Parosmylus prominens Needham, 1909 (Neuroptera: Osmylidae) from India. 1750 records from Colección del Herbario de la Universidad de los Llanos. 1 records from Notes on slender species of the long-jawed spider genus Tetragnatha (Araneae Tetragnathidae) with description of three new species. 61547 records from Florida Keys Reef Visual Census 2010. 3 records from Immature stages and biology of the enigmatic oxyporine rove beetles, with new data on Oxyporus larvae from the Russian Far East (Coleoptera: Staphylinidae). 774 records from Museu de Ciències Naturals de Barcelona: MCNB-Malac. 3 records from Two new Exilisia Toulgoët, 1958 from mainland Africa (Lepidoptera, Erebidae, Arctiinae). 566 records from Leicestershire and Rutland Mature trees Inventory 2011. 10 records from Valentin Moser Bats. 92 records from Planktonic bacterial communities in the arctic Canada Basin and Kongsfjorden. 2 records from Review of Allanagrus Noyes & Valentine (Hymenoptera: Mymaridae) with a key to species. 62 records from Rare vascular plant species in North-West of Kostroma region, Russia. 4 records from Gynacantha dryadula sp. nov. from the Guiana Shield (Odonata, Anisoptera: Aeshnidae). 141 records from Draubiotop Lavamünd. 2 records from Taxonomy of the genus Pristidia Deeleman-Reinhold, 2001 (Araneae: Clubionidae) in China. 33560 records from Extracellular DNA marine sediment Targeted Locus (Loci). 549 records from Netzfluegler_Raw1. 384 records from "Schwarzwassertal" bei Pobershau. 55 records from Phytoplankton abundance in the Wadden Sea off List, Sylt, North Sea in 2008. 2041 records from marine metagenome Targeted Locus (Loci). 218 records from Plan de vertebrados de la Patagonia. 2 records from A revision of the genus Petta Malmgren, 1866 (Annelida: Pectinariidae), with two new species from deep waters of southeastern Australia, and comments on phylogeny of the family. 1170 records from Springtales from lichen communities at Kollåsen in Norway. 92 records from Birdrace_TerraCamper-Münster. 21 records from Murciélagos de la isla de Providencia. Expedición Seaflower 2019 proyecto Colombia BIO. 3 records from Triplophysa sanduensis, a new loach species of nemacheilid (Teleostei: Cypriniformes) from South China. 6 records from Four new species of the genus Pseudosubhimalus (Hemiptera: Cicadellidae) from the Indian subcontinent. 54 records from Swedish Malaise Trap Project (SMTP) - Sepsidae. 22 records from Description of lithologic section units of IODP Hole 325-M0054B. 2 records from New species, genera, families, and range extensions of freshwater bryozoans in Brazil: the tip of the iceberg?. 1142 records from AlgaTerra. 2015 records from LTB AVH data. 678 records from Records from the South Australian Seed Conservation Centre. 3 records from Descriptions of species of Acrobeles von Linstow, 1877 (Nematoda, Rhabditida, Cephalobidae) from Kelso Dunes, Mojave National Preserve, California, USA. 282235 records from Données acquises dans le cadre de l'activité du bureau d'étude BIOTOPE (1994 - 2013). 1 records from Reclustering the cluster flies (Diptera: Oestroidea, Polleniidae). 1 records from Endophallus structure: a promising tool for cryptic species identification in Timarcha Samouelle, 1819 (Coleoptera: Chrysomelidae: Chrysomelinae). 820 records from Molluscs in surface sediments off Sylt collected during HEINCKE cruise HE272. 68 records from Distribution of Aphrocallistes beatrix in the N. Atlantic. 95 records from Vegetación vascular terrestre, entomofauna y macrofauna de la Isla Cayo Serrana durante la Expedición Seaflower 2016 - Proyecto Colombia BIO. 12942 records from LPO_PACA_2017_12_18. 47 records from Abundance and community structure of birds breeding in Kalahari woodland used as rangeland. 76 records from Living Prairie Museum Manitoba Herbarium (LPMMBH). 86 records from HSU Vertebrate Museum Mammals Collection. 8 records from Moniliophyta del Herbario BAB (Instituto de Recursos Biológicos CIRN-INTA). 661 records from Targeting a portion of central European spider diversity for permanent preservation. 3151 records from Centre for Biodiversity Genomics (BIOUG) - Marine Invertebrates. 119 records from Pachliopta butterfly specimens at Museum Zoologi Bogor, Indonesia. 1 records from New Prionospio and Laubieriellus (Annelida: Spionidae) species from Southeastern Brazil. 3 records from Umbyquyra gen. nov., a new tarantula spider genus from the Neotropical region (Araneae, Mygalomorphae, Theraphosidae), with a description of eight new species. 37445 records from ADDOMEx. 6977 records from 2019_NSMK_PL_2. 1 records from The InBIO Barcoding Initiative Database: Wesmaelius (Kimninsia) nervosus (Neuroptera, Hemerobiidae): a new species of brown lacewing for the Portuguese fauna. 218 records from NRW Regional Data: all taxa (sensitive species only), West Wales. 1704 records from 成龍溼地魚類生態紀錄. 1 records from Hydroporus novacula sp. n. from Georgia (Caucasus) (Coleoptera, Dytiscidae Hydroporini) - the first terrestrial species of the genus?. 16260 records from Acoustic monitoring data of avian species inside and outside the evacuation zone of the Fukushima Daiichi power plant accident. 8 records from Rutilans. 63 records from Fauna acuática asociada al Humedal Costero Obregón, Guapi, Cauca - 2013. 76 records from SNH Invertebrate Site Condition Monitoring 2015: Lurgie Loch SSSI. 27 records from Monitoreo de mastofauna en corredores biológicos de Chiapas. 4348 records from UTEP Insects (Arctos). 1 records from Review of Cosmocomoidea (Hymenoptera: Mymaridae) from China, with descriptions of two new species. 2412 records from (Appendix 2) Distribution of generalized biologic, anthropogenic, and volcanic constituents in sediment samples collected between 1995 and 2010 in the San Francisco Bay coastal system. 626 records from GNOR-Projekt "Halbwilde Weidehaltung zwischen Kamp-Bornhofen und Kestert" und Umland. 73 records from Leicestershire Bryophyte Data. 10 records from Données naturalistes de DURON Cyril. 976 records from Collection Pisces SMF. 781 records from Coral Reef Evaluation and Monitoring Project Dry Tortugas 2016. 6 records from New species of grasshopper genus Aptoceras Bruner, 1908 (Orthoptera, Acrididae, Ommatolampidinae, Ommtolampidiini) from Iguaçu National Park (Southern Brazil), including a taxonomic key and distribution data. 18 records from "Biodiversidad en el valle de Cuatro Ciénegas". (Ácaros acuáticos). 3143 records from Metagenome data from DNA stable isotope probing of Stiffkey saltmarsh sediment microcosms to investigate methanogenesis from choline. 25 records from Type specimens in the Port Elizabeth Museum, South Africa, including the historically important Albany Museum collection. Part 2: Reptiles (Squamata). 270 records from Plantas de la expedición en el páramo de Rabanal, Boyacá - Proyecto Boyacá BIO. 17 records from Peces de la expedición en el páramo El Consuelo, Boyacá - Proyecto Boyacá BIO. 10286 records from Atlantic Reference Centre Museum of Canadian Atlantic Organisms - Invertebrates and Fishes Data. 229 records from Earthworms of mole burrows in the forest zone of Western Siberia. 3351 records from Macroinvertebrados y perifiton pertenecientes a cuatro regiones de Colombia. 1 records from A new western Canadian record of Epeoloides pilosulus (Cresson), with discussion of ecological associations, distribution and conservation status in Canada. 3 records from Records and redescription of a mygalomorph spider genus ignored for over 100 years with a new species: the genus Atmetochilus Simon, 1887 (Araneae Nemesiidae) in Thailand. 117 records from Finnish Floristic Database (Literature Sources). 911 records from Données du/de la naturaliste MOULIN Nicolas provenant de la base de donnée du SINP Île-de-France CETTIA. 4 records from Not endemic after all: Imparipecten Freeman, 1961 (Diptera: Chironomidae) described from the Neotropical Region. 1 records from A new species of Tiodus (Hemiptera, Cercopidae) with a key to species of the genus. 13157 records from Belgian Coccinellidae - Ladybird beetles in Belgium. 2 records from A new species of Micraspis Chevrolat (Coleoptera: Coccinellidae) from Arunachal Pradesh, India. 10192 records from Survey and monitoring records for Scottish Wildlife Trust reserves from reserve convenors and Trust volunteers - Verified data. 92 records from Kochertgraben II. 529 records from Records of otters from Site Condition Monitoring in Scotland 2011-2012. 230 records from Inventaire avifaune. 2 records from A new Paramathes Boursin, 1954 (Lepidoptera, Noctuidae) species from China. 25358571 records from iNaturalist Research-grade Observations. 4942 records from Abundances and biological traits of the juveniles salmon sampled in the survey of Salmon abundance Indices in the Nivelle river (France). 277 records from Aunar esfuerzos y recursos técnicos, económicos y humanos con el fin de adelantar acciones de investigación para estimar las poblaciones y monitorear en el tiempo la rana venenosa Oophaga lehmanni en la localidad La Cascada (Valle del Cauca). 9 records from Two new species of the Amphinemura sinensis group (Plecoptera: Nemouridae) from southern China. 65 records from Cuxhaven Schlosspark, Klasse 5e- Amandus-Abendroth-Gymnasium. 239 records from Données de LACOSTE F. (SAPROX). 506 records from DBRC Reptile Records 1950 - 2015. 3 records from Two new species of the genus Cataglyphis Foerster, 1850 (Hymenoptera: Formicidae) from Iran.. 100 records from Anfibios y reptiles de la desembocadura del caño Teracay en el río Tomo, Puerto Carreño, Vichada - Proyecto Colombia Bio. 11532 records from Inventaire des Mammifères marins de France (métropole et outre-mer). 19 records from Bohemannia auriciliella (Nepticulidae) specimen data. 4 records from Cirolana bambang, a distinctive new species of Cirolana Leach, 1818 (Crustacea: Isopoda: Cirolanidae) from Bitung, Indonesia. 12 records from Synopsis of world Discleroderma Kieffer (Hymenoptera, Bethylidae). 1 records from Description of Penia mantillerii sp. nov. (Coleoptera: Elateridae: Dimini), with a key to Penia species from Vietnam and nearby areas. 2 records from A review species of the genus Ceroplastes (Hemiptera: Coccomorpha: Coccidae) in China. 1083 records from Appalachian State University, I. W. Carpenter, Jr. Herbarium. 1 records from A new species and key to all known species of Confusacris Yin & Li, 1987 (Orthoptera: Acrididae) from China. 344 records from Superórden Dictyoptera del Museo de Entomología de la Universidad del Valle (Cali, Colombia). 3 records from Taxonomic notes on the genus Protanilla (Hymenoptera: Formicidae: Leptanillinae) from Taiwan. 2 records from A new kukri snake (Colubridae: Oligodon) from Hua Hin District, and the first record of O. deuvei from Thailand. 39 records from Données Racoon sur le territoire de la Guadeloupe. 187 records from Anfibios y Reptiles asociados a tres ventanas de la Orinoquia Colombiana - SULU I. 8 records from Données du naturaliste DUFRENE ERIC provenant de la base de donnée du SINP Île-de-France CETTIA. 35 records from Mittelriede Höhe Gliesmarode-Braunschweig. 73 records from Outer Hebrides Insect Records from Literature. 17 records from Comunidad de Herpetos presentes en el río Tutunendo, Municipio de Quibdó-Chocó. 10438 records from Spermatophyta specimens of Iwate Prefectural Museum. 5 records from To the knowledge of Oriental species of subgenus Pseudochlaeniellus Jeannel, 1949 (Coleoptera, Carabidae, Chlaenius). 217 records from Inventaire des odonates 2014. 297 records from Phenology of Liliace. 578 records from Macrobenthos in surface sediments off Sylt collected during HEINCKE cruise HE293. 16 records from Genética de la Conservación del Oso Andino en el Parque Nacional Natural Cordillera de los Picachos y área de amortiguación. 7 records from Coeliccia rolandorum sp. nov. from eastern Cambodia and southern Vietnam, the eastern relative of C. kazukoae Asahina, 1984 (Odonata: Platycnemididae). 1108 records from Marine algal flora of Flores and Corvo Islands, Azores. 2 records from Molecular phylogeny of Hiptage (Malpighiaceae) reveals a new species from Southwest China. 34 records from An update of morphological and distributional data of the genus Patrera Simon (Araneae: Anyphaenidae: Anyphaeninae) with the description of twenty-five new species from Colombia. 5 records from Five new species of the Acantholycosa - complex (Araneae: Lycosidae) from Mongolia. 132 records from Molluscus specimens of Toyohashi Museum of Natural History. 24 records from Four new Amynthas and Metaphire earthworm species from nine provinces in southern China. 12764 records from Anfibios y reptiles de las regiones 30 (Parque Natural Sierra Maderas del Carmen); 31 (Sierra El Burro-Río San Rodrigo); 36 (Sierra La Encantada); y 37 (Sierra El Pino), Coahuila. 1632 records from Phenology and biological traits of adult migrating shad (Alosa sp) sampled by trapping in the survey in the Nivelle river (France). 650 records from Insectivorous Bats of Gunung Mulu National Park, Malaysia. 269 records from données arachnologiques de CARR David. 1135 records from MarineGEO visual diver surveys of fish communities around Carrie Bow Cay, Belize, 2015. 2 records from A new species of the genus Verilus (Teleostei, Percomorpha, Acropomatidae) from Brazil. 40 records from Two new species of Ecpatia Turner, 1902, and the first records of Ecpatia sciachroa Hampson, 1926 and Ecpatia obscura Holloway, 2009 from Thailand (Lepidoptera: Noctuidae, Noctuinae). 180 records from Données du/de la naturaliste Biermé Claire provenant de la base de donnée du SINP Île-de-France CETTIA. 15296 records from SEWBReC Beetles (South East Wales). 48 records from Ruhrwiesen bei Neheim-Hüsten. 1047 records from HUEFS herbarium - Universidade Estadual de Feira de Santana - Herbário Virtual REFLORA. 293 records from Macrofauna, entomofauna y vegetación vascular de la Isla Cayo Serranilla durante la Expedición Seaflower 2017 - Proyecto Colombia BIO. 1 records from Review of the Paratydeidae (Acari: Prostigmata), with description of three new species. 1364 records from Colección de Crustáceos Decápodos y Estomatópodos del Centro Oceanográfico de Cádiz (CCDE-IEOCD). 54 records from Coleção de Ictiologia do Museu de Ciências Naturais da Universidade do Vale do Taquari - Univates (ZIUMCN-UNIVATES). 3226 records from Fungi of Costa Rica (INBio). 1153 records from Polyamine-transforming bacterioplankton in seawater. 270 records from ABC Matandwe Forest Reserve Vegetation Survey. 12695 records from Intermountain Herbarium (Vascular plants & algae). 1716 records from Bryophyte Collection of Natural History Museum and Institute, Chiba. 23855 records from RHS lily beetle (Lilioceris lilii) monitoring. 5 records from Description of Coeliccia natgeo sp. nov. from Central Vietnam with keys to the males and females of the hayashii-group (Odonata: Zygoptera: Platycnemididae). 5401 records from Données Lépidoptères de l'Auvergne transmises par Pascal Peyrache.. 1873 records from Microbial community structure of chronically polluted marine sediments from a cold region of the southern hemisphere. 990 records from Bacterial communities from Thrombolites of Lake Sarmiento. 1 records from Lacewings (Neuroptera) of Ireland. 91352 records from 臺灣兩棲類資源調查與教育宣導推廣計畫 Resources survey and education advocacy to promote for Taiwan amphibian resources. 8 records from New lineages of Lebinthini from Australia (Orthoptera: Gryllidae: Eneopterinae). 134 records from BIRDRACE Griffin Wood Warblers. 261 records from Données espèces -expertise IQE 3. 184 records from Kystfuruskoger 2015. 156 records from Deep-Sea holothurians (Echinodermata, Holothuroidea) of the Colombian Southern Caribbean Sea. 3 records from A contribution towards checklist of fungus gnats (Diptera, Diadocidiidae, Ditomyiidae, Bolitophilidae, Keroplatidae, Mycetophilidae) in Georgia, Transcaucasia. 10 records from Description of two new species of Regalana and a new genus of Gyponini (Hemiptera: Cicadellidade: Iassinae). 3 records from Taxonomic study of the genus Promalactis Meyrick, 1908 (Lepidoptera: Oecophoridae) VIII. The densimacularis species group, with descriptions of four new species. 1 records from Review of the genus Haba Semenov, 1954 (Hymenoptera Chrysididae) with the key to species. 8 records from Données opportunistes sur les odonates et les rhopalocères. 432 records from Fishes in MZNA-VERT: ecological assessment of the Guadalope river in Aliaga (Spain). 595 records from MBML-Mamiferos - Coleção de Mamíferos. 2 records from A new species of freshwater crab of the genus Himalayapotamon Pretzmann, 1966 (Decapoda, Brachyura: Potamidae: Potaminae) from Uttarakhand, northern India. 5 records from New records of the water mite genus Arrenurus Dugès, 1834 from South America (Acari: Hydrachnidia: Arrenuridae), with the description of five new species and one new subspecies. 4 records from A new species of Victrix Staudinger, 1879 from Kazakhstan (Lepidoptera, Noctuidae). 11 records from Sphyraena stellata, anew barracudafromthe Indo-Pacific, with redescriptionsofS. helleri Jenkins, 1901 and S. novaehollandiae Günther, 1860 (Perciformes: Sphyraenidae). 228 records from Données du naturaliste Arnaud Bak. 45 records from SNH Invertebrate Site Condition Monitoring of Beetle Assemblage Features 2015: Fannich Hills SSSI. 2 records from A new pea crab species of the genus Arcotheres Manning, 1993 (Crustacea: Decapoda: Brachyura: Pinnotheridae) from India. 670 records from Project for Reef Fish Monitoring. 5 records from An update on the spider genus Hexophthalma (Araneae: Sicariidae) in the Afrotropical region, with descriptions of new species. 553 records from Composición florística y estructura de una parcela permanente en bosques humedos tropicales del resguardo Emberá Chontadural, municipio de Mutatá, Antioquia. 4240 records from Derek Lott Coleoptera Dataset. 4124 records from Inventaire de la flore des ENS des Pyrénées-Atlantiques 2011-2012. 2 records from Données de Lépidoptères de Bruno DAUGET - Dépt des PYRENEES-ORIENTALES (66). 1262 records from JCT AVH data. 35 records from Macrohongos en el municipio de Medina, Cundinamarca - Proyecto Colombia Bio. 8458 records from Hymenoptera collection of the Finnish Museum of Natural History. 734 records from Peces presentes en la colección Ictiológica CIACOL asociados a la región de Mitú, cuenca media del Río Vaupés. 330 records from University of Tennessee Bryophyte Herbarium. 482 records from JOIw - Xiloteca Joinvillea. 361 records from Deep-sea Echinoderm report (Crinoidea, Asteroidea, Ophiuroidea, Echinoidea) in the South Colombian Caribbean. 80 records from Revision of the family Chasmocarcinidae Serène, 1964 (Crustacea, Brachyura, Goneplacoidea). 2 records from A new species of Paraproto (Crustacea: Amphipoda) from southern New SouthWales, Australia. 9 records from Three new taxa of the genus Cechetra Zolotuhin & Ryabov, 2012 (Lepidoptera, Sphingidae) from South-East Asia with notes on other species of the genus. 2336 records from Collembola of Prioksko-Terrasny Nature Reserve: multi-scale spatial distribution analysis in pine forests. 5053 records from LACM Invertebrate Paleontology. 1 records from Variability and distribution of the golden-headed weevil Compsus auricephalus (Say) (Curculionidae: Entiminae: Eustylini). 5 records from Ptilophora variabilis Hartig, 1968, bona species, and description of Ptilophora nebrodensis sp. n. from Sicily (Lepidoptera, Notodontidae). 19 records from Observations of three Idotea species (I. balthica, I. chelipes and I. granulosa) in Northern Europe, including the Baltic Sea - field data. 3 records from Medleria gen. nov. adds to the biodiversity of Flatidae (Hemiptera: Fulgoromorpha) in the island of Socotra. 375 records from CG04_2017_12_18. 694 records from EDP Baixo Sabor: Construction and Reservoir Filling Phases – Wolf, (Canis lupus) Wild Boar (Sus scrofa) and Roe Deer (Capreolus capreolus) [camera-trapping] - [2011-2014]. 718 records from Données du/de la naturaliste CUENIN Sibylle provenant de la base de donnée du SINP Île-de-France CETTIA. 589 records from Données du/de la naturaliste PIQUET Alison provenant de la base de donnée du SINP Île-de-France CETTIA. 735 records from Laubenheimer Bodenheimer Ried - von Stromtalwiesen und Flutrasen. 4 records from A new genus and new species of the leafhopper tribe Idiocerini (Hemiptera Cicadellidae: Eurymelinae). 3 records from Two new species of the genus Leptoderes Serville, 1838 (Orthoptera, Tettigoniidae) from China. 453 records from Bulletin de la Société Linnéenne de Bordeaux, Tome 146 (N.S) n° 39 (1), 2011 - Données faune. 4446 records from Données naturalistes d'Olivier GARGOMINY saisies sous cardObs. 3 records from The Neotropical cuckoo wasp genus Ipsiura Linsenmaier, 1959 (Hymenoptera: Chrysididae): revision of the species occurring in Brazil. 286 records from Inventory of the Heteroptera (Insecta: Hemiptera) in Komaba Campus of the University of Tokyo, a highly urbanized area in Japan. 228 records from FBIP: Identification of polychaetes used as bait. 83945 records from Denver Museum of Nature & Science - Entomology. 2 records from A new species of Athaumasta Hampson, 1906 (Lepidoptera, Noctuidae, Bryophilinae) from the Altai Mountains of Mongolia and China. 6 records from Swedish Malaise Trap Project (SMTP) - Strepsiptera. 7 records from The millipede family Paradoxosomatidae in the Philippines, with a description of Eustrongylosoma penevi sp.n., and notes on Anoplodesmus anthracinus Pocock, 1895, recorded in Malaysia and Sri Lanka for the first time (Diplopoda, Polydesmida). 2084 records from Occurrence data of tree species for crystalline Mountain Forest of Tanzania.. 10 records from New species of Australian microgastrine parasitoid wasps (Hymenoptera: Braconidae: Microgastrinae) documented through the ‘ Bush Blitz’ surveys of national reserves. 62 records from NEON Invertebrate Voucher Collection at Arizona State University. 513 records from Estado actual de conservación de liebres y conejos en categoría de riesgo en México. 42 records from (Table 1) Abundance, wet biomass, and carbon biomass of all major groups of phytoplankton in the water column of the Kara Sea. 7166 records from Fish Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 16047 records from Database for alien invasive plants occurrences in Germany. 2 records from A new pygmy squid, Idiosepius hallami n. sp. (Cephalopoda: Idiosepiidae) from eastern Australia and elevation of the southern endemic ‘ notoides’ clade to a new genus, Xipholeptos n. gen.. 66 records from Capture of Primary Biodiversity Data for West African Plants. 31 records from A revision of the grunter genus Syncomistes (Teleostei, Terapontidae, Syncomistes) with descriptions
Keywords: GBIF; biodiversity; species occurrences